Polishing pad with reduced defect generation and method of preparing semiconductor device using the same
Patent Information
- Application Number
- JP2024106264
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-11-06
- Filing Date
- 2024-07-01
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2044-07-01
AI Technical Summary
【0016】 前記実現例による研磨パッドは、これにより得られるデブリのサイズとゼータ電位特性とが、特定範囲内に調整されることにより、研磨パッドの諸物性と性能を優れた状態で保ちながらも、CMP工程の際に欠陥およびスクラッチの発生を最小化し得る。
Smart Images

Figure 2025018957000001_ABST
Abstract
Description
[Technical field]
[0001] The embodiment relates to a polishing pad capable of reducing defects and scratches during a chemical mechanical planarization (CMP) process and a method for manufacturing a semiconductor device using the same. [Background technology]
[0002] Among semiconductor manufacturing processes, the chemical mechanical planarization (CMP) process is a process in which a semiconductor substrate such as a wafer is attached to a head and brought into contact with the surface of a polishing pad formed on a platen, and a slurry is supplied to chemically react with the semiconductor substrate surface while the platen and head are moved relative to each other to mechanically planarize uneven portions of the semiconductor substrate surface.
[0003] Polishing pads are essential components that play an important role in such CMP processes. They are usually made of polyurethane resin and have grooves on their surface that allow for large slurry flow and pores that support fine flow.
[0004] To manufacture the polishing pad, a prepolymer is obtained by reacting diisocyanate with a polyol, and then a curing agent and a foaming agent are mixed with the prepolymer and cured to obtain a polyurethane foam sheet. The polyurethane foam sheet is then sliced at the top and bottom to obtain an upper pad according to the desired thickness, and a groove is formed on the surface of the upper pad by digging a groove in a specific shape using a tip or the like, and then the upper pad is bonded to a polyurethane-based lower pad to complete the polishing pad.
[0005] The CMP process can be applied in multiple ways in the manufacturing process of semiconductor devices. In the case of semiconductor devices, the device includes multiple layers, each of which includes a complex and fine circuit pattern. In recent years, the size of individual chips in semiconductor devices has been reduced, and the patterns of each layer have been made more complex and fine. As a result, the purpose of the CMP process in the manufacturing process of semiconductor devices has expanded beyond the planarization of circuit wiring to include the separation of circuit wiring and the improvement of wiring surfaces, and as a result, more sophisticated and reliable CMP performance is required.
[0006] During the CMP process of such a polishing pad, debris is generated when the polishing surface is rubbed against the semiconductor substrate or when the polishing surface is cut by a diamond disk for conditioning. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Korean Patent Publication No. 2016-0027075 Summary of the Invention [Problem to be solved by the invention]
[0008] During the CMP process of the polishing pad, debris is generated during the friction process between the polishing surface and the semiconductor substrate, or when the polishing surface is cut by a diamond disk for conditioning. Such debris induces defects and scratches on the polishing surface during the CMP process.
[0009] As a result of the inventors' research, they found that the size and zeta potential characteristics of the debris obtained from the polishing pad affect the occurrence of defects, and by adjusting the above characteristics within a certain range, they were able to minimize the occurrence of defects and scratches during the CMP process while maintaining the various physical properties and performance of the polishing pad in an excellent state.
[0010] Furthermore, as a result of the inventors' research, it was possible to realize a polishing pad in which the particle size of debris is reduced by irradiating UV light during the CMP process, and by utilizing the characteristics of this polishing pad and irradiating UV light during the CMP process, it was possible to minimize the occurrence of defects and scratches in semiconductor devices.
[0011] Therefore, a problem to be solved relates to a polishing pad with reduced defect generation and a method for manufacturing a semiconductor device using the same. [Means for solving the problem]
[0012] According to one embodiment, a polishing pad is provided that includes an abrasive layer, the polishing layer including a urethane-based prepolymer, a foaming agent, and a curing agent, and when the polishing layer is conditioned for 10 minutes under conditions of a platen speed of 93 rpm, a conditioner load of 9 lb, a conditioner speed of 64 rpm, and 19 sweeps / min while supplying 300 cc / min of deionized water, the D50 particle size of the resulting debris is 50 μm or less under pH 5.5 conditions, and the zeta potential of an aqueous solution containing the debris at a concentration of 0.01 wt% is -20 mV to 30 mV under pH 5.5 conditions.
[0013] In another embodiment, a polishing pad is provided which includes a polishing layer containing a polyurethane resin, and the polishing layer is conditioned under conditions of a platen speed of 93 rpm, a conditioner load of 9 lb, a conditioner speed of 64 rpm, and 19 sweeps / min while supplying 250 mL / min of ceria slurry, and then irradiated with UV light having a wavelength of 100 nm to 380 nm at an intensity of 1 kW from a distance of 5 cm, whereby the debris obtained satisfies the following formula (1): D50[0 minutes]>D50[4 minutes]...(1) Here, D50[0 min] is the D50 particle size of the debris obtained by conditioning before the UV light irradiation, and D50[4 min] is the D50 particle size of the debris obtained when irradiated with UV light for 4 minutes after the conditioning.
[0014] According to another embodiment, a method for manufacturing a semiconductor device is provided, the method including polishing a surface of a semiconductor substrate using the polishing pad.
[0015] According to another embodiment, a method for manufacturing a semiconductor device is provided, which includes a step of conditioning a polishing layer of the polishing pad by irradiating UV light having a wavelength of 100 nm to 380 nm while chemically mechanically polishing a semiconductor substrate using the polishing pad. Effect of the Invention
[0016] The polishing pad according to the above embodiment can minimize the occurrence of defects and scratches during the CMP process while maintaining excellent physical properties and performance of the polishing pad by adjusting the size and zeta potential characteristics of the resulting debris within a specific range.
[0017] The polishing pad according to the embodiment has a characteristic that the particle size of debris is reduced by irradiating UV light during the CMP process, and thus the occurrence of defects and scratches in semiconductor devices can be minimized by irradiating UV light during the CMP process using the characteristic of the polishing pad. In addition, the polishing pad according to the embodiment has excellent characteristics such as polishing rate, and therefore, when manufacturing semiconductor devices using the polishing pad, the CMP performance and yield can be improved. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a semiconductor device manufacturing process using a polishing pad according to one implementation. [Diagram 2] FIG. 2 is a diagram showing the occurrence of defects due to debris during the semiconductor device manufacturing process. [Diagram 3] FIG. 3 is a method for measuring particle size of debris obtained from a polishing pad according to one implementation. [Figure 4] FIG. 4 is a method for measuring the zeta potential of an aqueous debris solution obtained from a polishing pad according to one implementation. [Diagram 5]FIG. 5 is a diagram showing the change in particle size of debris obtained from the polishing pad according to the embodiment depending on the UV irradiation time. [Figure 6] FIG. 6 is a diagram showing the change in particle size of debris obtained from a polishing pad according to a comparative example depending on the UV irradiation time. [Figure 7] FIG. 7 is a diagram showing the configuration of an apparatus for irradiating UV light during a CMP process according to one implementation. [Figure 8] FIG. 8 is a diagram showing the configuration of an apparatus for irradiating UV light during a CMP process according to one implementation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Various implementations and embodiments will now be described in detail with reference to the drawings.
[0020] In describing the implementation examples, if a detailed description of related known configurations or functions is determined to make the gist of the implementation example unclear, the detailed description will be omitted. In addition, the size of each component in the drawings may be exaggerated or omitted for the purpose of explanation, and may differ from the size actually applied.
[0021] In this specification, a description that one component is formed above / below another component, or is connected or joined to each other includes being formed, connected or joined directly between these components, or indirectly through other components. It should be understood that the reference regarding the above / below of each component may change depending on the direction in which the object is observed.
[0022] In this specification, the terms referring to each component are used to distinguish it from other components and are not intended to limit the implementation examples. Furthermore, in this specification, the singular expression includes the plural expression unless the context clearly indicates otherwise.
[0023] In this specification, the terms "first", "second", etc. are used to describe various components, and the components should not be limited by the terms. The terms are used for the purpose of distinguishing one component from another.
[0024] In this specification, the term "comprising" is intended to embody certain features, regions, steps, steps, elements and / or components, and does not exclude the presence or inclusion of other features, regions, steps, steps, elements and / or components therein, unless specifically stated to the contrary.
[0025] The molecular weights of the compounds and polymers described herein, for example, number average molecular weight or weight average molecular weight, are, as is well known, expressed as relative masses based on carbon-12 without units, but may be understood to be the same numerical molar mass (g / mol) as necessary.
[0026] In the numerical ranges limiting the size, physical properties, etc. of the components described in this specification, when a numerical range limited only by an upper limit value and a numerical range limited only by a lower limit value are separately exemplified, it should be understood that the numerical range combining these upper and lower limits is also included in the exemplary range.
[0027] [Chemical mechanical polishing] Semiconductor devices are manufactured by chemical mechanical polishing using a polishing pad. According to one implementation, a method for manufacturing a semiconductor device includes polishing a surface of a semiconductor substrate with a polishing pad.
[0028] Specifically, the method for manufacturing the semiconductor device may include providing a polishing pad according to the embodiment, and polishing the surface of the semiconductor substrate by rotating the polishing pad relative to each other so that the polishing surface of the polishing layer and the surface of the semiconductor substrate abut against each other.
[0029] 1 is a diagram showing a semiconductor device manufacturing process using a polishing pad according to an embodiment. Referring to FIG. 1, a polishing pad 100 according to an embodiment is mounted on a platen 200, and then a semiconductor substrate 600 to be polished is placed on the polishing pad 100. At this time, the surface to be polished of the semiconductor substrate 600 directly contacts the polishing surface of the polishing pad 100. For polishing, a polishing slurry 450 may be sprayed onto the polishing pad through a nozzle. The flow rate of the polishing slurry 450 supplied through the nozzle is about 10 cm. 3 / min ~ approx. 1000cm 3 / min. can be selected according to the purpose. For example, about 50 cm 3 / min ~ approx. 500cm 3 / min, but is not limited to this.
[0030] Thereafter, the semiconductor substrate 600 and the polishing pad 100 may rotate relative to each other to polish the surface of the semiconductor substrate 600. At this time, the rotating direction of the semiconductor substrate 600 and the rotating direction of the polishing pad 100 may be the same or opposite to each other. The rotating speeds of the semiconductor substrate 600 and the polishing pad 100 may be selected according to the purpose within a range of about 10 rpm to about 500 rpm, respectively, and may be, for example, about 30 rpm to about 200 rpm, but are not limited thereto.
[0031] The semiconductor substrate 600, when attached to the polishing head 510, is pressed against the polishing surface of the polishing pad 100 with a predetermined load, and the surface of the semiconductor substrate 600 is polished. The load applied by the polishing head 510 to the surface of the semiconductor substrate 600 and the polishing surface of the polishing pad 100 is about 1 gf / cm. 2 ~About 1000gf / cm 2 can be selected according to the purpose, for example, about 10 gf / cm 2 ~About 800gf / cm 2 It may be, but is not limited to this.
[0032] In one embodiment, the semiconductor substrate 600 to be polished may include an oxide film, a tungsten film, or a composite film thereof. Specifically, the semiconductor substrate 600 may include an oxide film, a tungsten film, or a composite film of an oxide film and a tungsten film. The composite film of an oxide film and a tungsten film may be a multi-layer film in which the tungsten film is stacked on one side of the oxide film, or may be a single layer film in which an oxide region and a tungsten region are mixed in one layer. Since the polishing object has such film quality characteristics and the polishing pad has the characteristics according to the embodiment, defects in the semiconductor device manufactured by the manufacturing method of the semiconductor device may be minimized.
[0033] In one embodiment, the method for manufacturing a semiconductor device may further include, in the step of polishing the object to be polished, a step of supplying either the oxide film polishing slurry or the tungsten film polishing slurry, or a step of sequentially supplying the oxide film polishing slurry and the tungsten film polishing slurry to a polishing surface.
[0034] For example, when the semiconductor substrate to be polished includes an oxide film, the method for manufacturing a semiconductor device may include a step of supplying the oxide film polishing slurry. When the semiconductor substrate includes a tungsten film, the method for manufacturing a semiconductor device may include a step of supplying the tungsten film polishing slurry. When the semiconductor substrate includes a composite film of an oxide film and a tungsten film, the method for manufacturing a semiconductor device may include a step of supplying the oxide film polishing slurry and the tungsten film polishing slurry sequentially to the polishing surface. At this time, depending on the process, the oxide film polishing slurry may be supplied first and then the tungsten film polishing slurry may be supplied later, or the tungsten film polishing slurry may be supplied first and then the oxide film polishing slurry may be supplied later.
[0035] In one embodiment, the method for manufacturing a semiconductor device may further include a step of processing the polishing surface of the polishing pad 100 with a conditioner 300 simultaneously with polishing the semiconductor substrate 600 in order to maintain the polishing surface of the polishing pad 100 in a state suitable for polishing.
[0036] In the polishing pad according to one embodiment, the size and zeta potential characteristics of the debris obtained from the polishing layer are adjusted within a specific range, thereby minimizing the occurrence of defects and scratches during the CMP process while maintaining the various physical properties and performance of the polishing pad in excellent condition, and therefore semiconductor devices of high quality can be efficiently manufactured using the polishing pad.
[0037] [Polishing pad] According to one embodiment, the polishing pad includes a polishing layer, the polishing layer including a polyurethane resin.
[0038] Specifically, the polishing pad includes a polishing layer and a support layer, and an adhesive layer may be interposed between the polishing layer and the support layer.
[0039] 2 is a diagram showing defects caused by debris during the manufacturing process of a semiconductor device. Referring to FIG. 2, defects 650 and scratches are caused on the surface of the semiconductor device by debris 150 generated from the polishing layer, but according to one embodiment, the size and zeta potential of the debris generated from the polishing layer can be adjusted within a specific range to minimize the occurrence of defects and scratches.
[0040] In one implementation, the polishing pad provides debris having a particular range of particle sizes.
[0041] 3 is a diagram showing a method for measuring the particle size of debris obtained from a polishing pad according to an embodiment. Referring to FIG. 3, a polishing pad is attached and set on the platen of a CMP polishing device, and the polishing layer is conditioned while supplying deionized water, and debris of the polishing layer generated after 10 minutes of conditioning can be collected in a solution state mixed with deionized water. The pH of the debris aqueous solution can be adjusted using an aqueous nitric acid solution or an aqueous potassium hydroxide solution, and the particle size of the debris can be measured using a particle size analyzer.
[0042] Specifically, the debris was obtained when conditioning the polishing layer of the polishing pad under the conditions of a platen speed of 93 rpm, a conditioner load of 9 lb, a conditioner speed of 64 rpm, and 19 sweeps / min while supplying 300 cc / min of deionized water, and the particle size of the debris may be an average particle size, i.e., a D50 particle size. As a specific example, the conditioner may be a diamond disk (e.g., a CI45 type disk from Sesol) with a pad cut rate (PCR) of 80 μm / hr to 90 μm / hr.
[0043] According to one implementation example, the D50 particle size of the debris obtained when conditioning the polishing layer under the above conditions for 10 minutes is 50 μm or less under pH 5.5 conditions.
[0044] Specifically, the D50 particle size of the debris obtained when conditioning the polishing layer for 10 minutes under the above conditions may be 40 μm or less, 30 μm or less, 25 μm or less, 22 μm or less, 20 μm or less, 19 μm or less, 18 μm or less, or 17 μm or less under pH 5.5 conditions, and may also be 5 μm or more, 10 μm or more, or 15 μm or more.
[0045] More specifically, the D50 particle size of the debris obtained when conditioning the polishing layer under the above conditions for 10 minutes can be 10 μm to 50 μm, 10 μm to 40 μm, 10 μm to 30 μm, 10 μm to 25 μm, 10 μm to 22 μm, 10 μm to 21 μm, 10 μm to 20 μm, 10 μm to 19 μm, 10 μm to 18 μm, or 10 μm to 17 μm under pH 5.5 conditions.
[0046] According to another embodiment, the D50 particle size of the debris obtained when conditioning the polishing layer under the above conditions for 10 minutes is 35 μm or less under pH 10 conditions.
[0047] Specifically, the D50 particle size of the debris obtained when conditioning the polishing layer for 10 minutes under the above conditions may be 35 μm or less, 30 μm or less, 25 μm or less, 24 μm or less, 23 μm or less, 22.3 μm or less, 22 μm or less, or 21 μm or less under pH 10 conditions, and may also be 5 μm or more, 10 μm or more, 15 μm or more, or 20 μm or more.
[0048] More specifically, the D50 particle size of the debris obtained when conditioning the polishing layer under the above conditions for 10 minutes can be 15 μm to 35 μm, 15 μm to 30 μm, 15 μm to 25 μm, 15 μm to 24 μm, 15 μm to 23 μm, 15 μm to 22.3 μm, 15 μm to 22 μm, or 15 μm to 21 μm under pH 10 conditions.
[0049] According to one specific example, the D50 particle size of the debris obtained when conditioning the polishing layer may be 25 μm or less under pH 5.5 conditions and 22.3 μm or less under pH 10 conditions.
[0050] Within the preferred particle size range, the occurrence of defects and scratches during the CMP process can be minimized while maintaining the various physical properties and performance of the polishing pad in excellent condition.
[0051] Additionally, polishing pads according to the above implementations may result in an aqueous solution of debris having a particular range of zeta potential.
[0052] FIG. 4 is a method for measuring the zeta potential of a debris aqueous solution obtained from a polishing pad according to an embodiment. Referring to FIG. 4, a polishing pad is attached and set on a platen of a CMP polishing device, and the polishing layer is conditioned while supplying deionized water, and debris of the polishing layer generated after 10 minutes of conditioning may be collected in a solution state mixed with deionized water. For particle stability of the debris aqueous solution, the solution may be stored at room temperature for 24 hours to precipitate particles with a diameter of 20 μm or more, and the supernatant located within 10 mm from the upper surface of the solution may be collected as a sample. Thereafter, the pH of the sample may be adjusted using an aqueous nitric acid solution or an aqueous potassium hydroxide solution, and the zeta potential of the sample may be measured using a zetasizer. The sample may contain debris at a concentration of 0.01% by weight.
[0053] As an example, the zeta potential of an aqueous solution containing debris at a concentration of 0.01 wt % obtained when conditioning the polishing layer under the above conditions for 10 minutes may be, under pH 5.5 conditions, -20 mV or more, -15 mV or more, -10 mV or more, -5 mV or more, 0 mV or more, 5 mV or more, or 10 mV or more, and may be 50 mV or less, 40 mV or less, 30 mV or less, 20 mV or less, 15 mV or less, or 10 mV or less.
[0054] According to one embodiment, the zeta potential of an aqueous solution containing debris at a concentration of 0.01% by weight obtained when conditioning the polishing layer for 10 minutes under the above conditions is −20 mV to 30 mV under pH 5.5 conditions.
[0055] Specifically, the zeta potential of an aqueous solution containing debris at a concentration of 0.01% by weight obtained when conditioning the polishing layer for 10 minutes under the above conditions can be −15 mV to 25 mV, −10 mV to 25 mV, −10 mV to 20 mV, −10 mV to 15 mV, −5 mV to 30 mV, or 0 mV to 30 mV under pH 5.5 conditions.
[0056] More specifically, the zeta potential of an aqueous solution of said debris may be a positive (+) value.
[0057] Within the desired range, the zeta potential of the debris is similar to that of the abrasive particles (e.g., ceria particles) in the CMP polishing composition (slurry), and the occurrence of defects can be further reduced. Specifically, the zeta potential quantitatively represents the magnitude of the repulsive and attractive forces between particles generated by the cations / anions of the particles in the suspension, and when the zeta potentials of the debris and the abrasive particles are similar, the repulsive forces between the particles increase, preventing aggregation, and the particle size in the composition can be reduced to reduce the occurrence of defects and scratches.
[0058] As another example, the zeta potential of an aqueous solution containing debris at a concentration of 0.01 wt % obtained when conditioning the polishing layer for 10 minutes under the above conditions may be, under pH 10 conditions, -50 mV or more, -45 mV or more, -40 mV or more, -35 mV or more, or -30 mV or more, and may also be 30 mV or less, 20 mV or less, 10 mV or less, 0 mV or less, -10 mV or less, or -20 mV or less.
[0059] Specifically, the zeta potential of an aqueous solution containing debris at a concentration of 0.01% by weight obtained when conditioning the polishing layer for 10 minutes under the above conditions can be −50 mV to −10 mV under pH 10 conditions.
[0060] More specifically, the zeta potential of an aqueous solution containing debris at a concentration of 0.01% by weight obtained when conditioning the polishing layer for 10 minutes under the above conditions can be -50 mV to -15 mV, -50 mV to -20 mV, -50 mV to -25 mV, -40 mV to -10 mV, or -30 mV to -10 mV under pH 10 conditions.
[0061] Furthermore, the polishing pad has a certain relationship between the particle size of the debris and the zeta potential under pH conditions, so that the effect can be further improved.
[0062] According to one implementation, the value of the following formula (1) may be −20 μm / mV to 30 μm / mV, and in one specific example, −10 μm / mV to 20 μm / mV. D50[5.5] / Zp[5.5]...(1) Here, D50[5.5] is the D50 particle size (μm) of the debris obtained when conditioning the polishing layer under pH 5.5 conditions, and Zp[5.5] is the zeta potential (mV) of an aqueous solution containing the debris obtained when conditioning the polishing layer at a concentration of 0.01 wt % under pH 5.5 conditions.
[0063] For example, the value of the formula (1) may be -20 μm / mV or more, -10 μm / mV or more, -5 μm / mV or more, or 0 μm / mV or more, and may be 30 μm / mV or less, 20 μm / mV or less, 15 μm / mV or less, 10 μm / mV or less, or 5 μm / mV or less. Specifically, the value of the formula (1) may be -10 μm / mV to 15 μm / mV, -5 μm / mV to 20 μm / mV, -5 μm / mV to 15 μm / mV, 0 μm / mV to 15 μm / mV, -5 μm / mV to 10 μm / mV, 0 μm / mV to 10 μm / mV, -5 μm / mV to 5 μm / mV, or 0 μm / mV to 5 μm / mV.
[0064] According to another implementation, the value of the following formula (2) may be 60% to 120%, and in one specific example, 70% to 110%. (D50[5.5] / D50
[10] )×100...(2) Here, D50[5.5] is the D50 particle size (μm) of the debris obtained when conditioning the polishing layer under a pH of 5.5 condition, and D50
[10] is the D50 particle size (μm) of the debris obtained when conditioning the polishing layer under a pH of 10 condition.
[0065] For example, the value of the formula (2) may be 60% or more, 70% or more, or 75% or more, and may be 120% or less, 110% or less, 105% or less, 100% or less, 95% or less, 90% or less, 85% or less, or 80% or less. Specifically, the value of the formula (2) may be 70% to 105%, 70% to 100%, 70% to 95%, 70% to 90%, 70% to 85%, or 75% to 85%.
[0066] According to another embodiment, the value of the following formula (3) may be 25 mV to 65 mV, and in one specific example, 35.5 mV to 60 mV. Zp[5.5]-Zp
[10] ...(3) Here, Zp[5.5] is the zeta potential (mV) of an aqueous solution containing the debris obtained during conditioning of the polishing layer at a concentration of 0.01% by weight at pH 5.5, and Zp
[10] is the zeta potential (mV) of an aqueous solution containing the debris obtained during conditioning of the polishing layer at a concentration of 0.01% by weight at pH 10.
[0067] For example, the value of the formula (3) may be 25 mV or more, 35.5 mV or more, or 36 mV or more, and 65 mV or less, 60 mV or less, 55 mV or less, 50 mV or less, or 45 mV or less. Specifically, the value of the formula (3) may be 35.5 mV to 55 mV, 35.5 mV to 50 mV, 35.5 mV to 45 mV, 35.5 mV to 40 mV, 36 mV to 60 mV, 36 mV to 50 mV, 36 mV to 45 mV, or 36 mV to 40 mV.
[0068] Furthermore, the polishing pad according to the above embodiment has excellent performance and physical properties.
[0069] For example, when the polishing pad is used to polish a silicon oxide film of a silicon wafer with a ceria slurry, the removal rate may be 2000 Å / min or more, 2200 Å / min or more, 2300 Å / min or more, or 2400 Å / min or more, and may be 3000 Å / min or less, 2800 Å / min or less, 2600 Å / min or less, or 2500 Å / min or less.
[0070] As a specific example, when the polishing pad is used to polish a silicon oxide film of a silicon wafer with a ceria slurry, the polishing rate according to the following Equation 1 may be 2200 Å / min to 2600 Å / min. [Number 1] Polishing rate (Å / min) = change in film thickness before and after polishing (Å) / polishing time (min)
[0071] Specifically, the polishing rate may be a polishing rate for a silicon wafer having a diameter of 300 mm on which silicon oxide is deposited. The polishing rate may be measured while rotating the platen at 150 rpm for 60 seconds while feeding the calcined ceria slurry at 250 mL / min under the conditions of a polishing load of 4.0 psi and a polishing pad rotation speed of 150 rpm. The temperature condition during the measurement of the polishing rate is not particularly limited, and may be, for example, room temperature.
[0072] Additionally, the pad cutting rate of the polishing layer may be 30 μm / hr to 60 μm / hr, 30 μm / hr to 50 μm / hr, 40 μm / hr to 60 μm / hr, or 40 μm / hr to 50 μm / hr.
[0073] The thickness of the polishing pad may be 0.8 mm to 5.0 mm, 1.0 mm to 4.0 mm, 1.0 mm to 3.0 mm, 1.5 mm to 2.5 mm, 1.7 mm to 2.3 mm, or 2.0 mm to 2.1 mm. When the thickness is within the above range, the particle size deviation between the upper and lower parts of the pores is minimized, and the basic physical properties of the polishing pad can be sufficiently exhibited.
[0074] [Polishing pad characteristics when exposed to UV light] In one embodiment, the polishing pad has a characteristic that the debris particle size is reduced by irradiating UV light during the CMP process, and by utilizing such a characteristic of the polishing pad, the occurrence of defects and scratches in semiconductor elements can be minimized by irradiating UV light during the CMP process.
[0075] 5 and 6 show the change in particle size of debris obtained from the polishing pads according to the example and the comparative example with respect to UV irradiation time, respectively.
[0076] 5, the polishing pad according to the embodiment shows that the debris particle size decreases as the UV light irradiation time elapses, being the smallest after 2 to 4 minutes, and then shows a tendency to increase slightly after 6 to 8 minutes of UV light irradiation, but overall the debris particle size shows a tendency to decrease as the UV light irradiation time elapses. On the other hand, the polishing pad according to the comparative example shows a tendency to generally increase the debris particle size as the UV light irradiation time elapses, and after 10 minutes it was measured to be nearly twice as large as the initial size.
[0077] During UV irradiation, molecular bonds are broken and particles aggregate, and depending on which of these phenomena prevails, the particle size of the debris may tend to increase or decrease. This tendency may be dependent on the composition and characteristics of the polishing pad.
[0078] In order to measure the particle size of the debris, a polishing pad is attached and set on the platen of a CMP polishing device, the polishing layer is conditioned while supplying CMP slurry, and the debris of the polishing layer generated 10 minutes after conditioning is collected in a solution state mixed with the CMP slurry. After that, the debris solution is irradiated with UV light having a wavelength of 100 nm to 380 nm at an intensity of 1 kW from a predetermined distance, and the particle size of the debris is measured using a particle size analyzer.
[0079] Specifically, the debris was obtained when conditioning the polishing layer of the polishing pad under the conditions of a platen speed of 93 rpm, a conditioner load of 9 lb, a conditioner speed of 64 rpm, and 19 sweeps / min while supplying 250 ml / min of ceria slurry, and the particle size of the debris may be an average particle size, i.e., a D50 particle size. As a specific example, the conditioner may be a diamond disk (e.g., a CI45 type disk from Sesol) with a pad wear rate (PWR) of 80 μm / hr to 90 μm / hr.
[0080] In one embodiment of the polishing pad, the polishing layer is conditioned under conditions of a platen speed of 93 rpm, a conditioner load of 9 lb, a conditioner speed of 64 rpm, and 19 sweeps / min while supplying 250 mL / min of ceria slurry, and then irradiated with UV light having a wavelength of 100 nm to 380 nm at an intensity of 1 kW from a distance of 5 cm, such that the debris obtained satisfies the following formula (1). D50[0 minutes]>D50[4 minutes]...(1) Here, D50[0 min] is the D50 particle size of the debris obtained by conditioning before the UV light irradiation, and D50[4 min] is the D50 particle size of the debris obtained when irradiated with UV light for 4 minutes after the conditioning.
[0081] In particular, in the formula (1), the difference between D50[0 min] and D50[4 min] may be at a certain level or more. For example, if ΔD50[0-4 min] calculated by the following formula is 5 μm or more, it is more advantageous in terms of the effect of reducing debris by UV irradiation.
[0082] D50[0-4 minutes]=D50[0 minutes]-D50[4 minutes] Here, D50[0 min] is the D50 particle size of the debris obtained by conditioning before the UV light irradiation, and D50[4 min] is the D50 particle size of the debris obtained when irradiated with UV light for 4 minutes after the conditioning.
[0083] Specifically, the ΔD50[0 - 4 min] is 5 μm or more, 7 μm or more, 10 μm or more, or 13 μm or more, and can be 35 μm or less, 30 μm or less, 25 μm or less, or 20 μm or less. More specifically, the ΔD50[0 - 4 min] can be 5 μm to 30 μm, 5 μm to 25 μm, 10 μm to 30 μm, or 10 μm to 25 μm.
[0084] The D50[4 min] is, for example, 40 μm or less, 35 μm or less, 30 μm or less, 27 μm or less, or 25 μm or less, and can be 5 μm or more, 10 μm or more, 15 μm or more, or 20 μm or more. As a specific example, the D50[4 min] can be 30 μm or less. As a more specific example, the D50[4 min] can be 5 μm to 30 μm. Within the preferred range, the occurrence of defects in the semiconductor element due to debris can be further minimized.
[0085] The D50[0 min] is, for example, 20 μm or more, 25 μm or more, 30 μm or more, or 35 μm or more, and can be 65 μm or less, 60 μm or less, 55 μm or less, or 45 μm or less. Specifically, the D50[0 min] can be 20 μm to 60 μm or 30 μm to 50 μm. More specifically, the D50[0 min] can be 35 μm or more, and the D50[4 min] can be 30 μm or less.
[0086] In other embodiments, the polishing pad may satisfy the following formula (2). D50[4 min]<D50[8 min]...(2) Here, D50[4 min] is the D50 particle size of the debris obtained when irradiating UV light for 4 minutes after the conditioning, and D50[8 min] is the D50 particle size of the debris obtained when irradiating UV light for 8 minutes after the conditioning.
[0087] In the formula (2), the difference between D50[8min] and D50[4min] may be within a certain range. For example, it is advantageous for ΔD50[8-4min] calculated by the following formula to be 20μm or less in order to maintain the tendency of the debris particle size to decrease due to UV irradiation. △D50[8-4 minutes]=D50[8 minutes]-D50[4 minutes] Here, D50[4min] is the D50 particle size of the debris obtained when irradiated with UV light for 4 minutes after the conditioning, and D50[8min] is the D50 particle size of the debris obtained when irradiated with UV light for 8 minutes after the conditioning.
[0088] Specifically, the ΔD50[8-4 min] may be 20 μm or less, 15 μm or less, or 10 μm or less, and may be 3 μm or more, or 5 μm or more. More specifically, the ΔD50[8-4 min] may be 3 μm to 20 μm, 3 μm to 15 μm, 3 μm to 10 μm, or 5 μm to 15 μm.
[0089] The D50[8 min] may be, for example, 55 μm or less, 50 μm or less, 45 μm or less, or 40 μm or less, or 15 μm or more, 20 μm or more, 25 μm or more, or 30 μm or more. Specifically, the D50[8 min] may be 20 μm to 50 μm or 25 μm to 40 μm.
[0090] More specifically, the D50[8 min] may be 30 μm to 40 μm, and the D50[4 min] may be 20 μm to 30 μm.
[0091] In yet another embodiment, the polishing pad may satisfy the following formula (3): (D90[0 min]-D10[0 min])>(D90[4 min]-D10[4 min])...(3) Here, D10[0 min] and D90[0 min] are the D10 and D90 particle sizes of the debris obtained by conditioning before the UV irradiation, and D10[4 min] and D90[4 min] are the D10 and D90 particle sizes of the debris obtained when irradiated with UV light for 4 minutes after the conditioning.
[0092] In the formula (3), the difference between (D90[0 min]-D10[0 min]) and (D90[4 min]-D10[4 min]) may be equal to or greater than a certain level.
[0093] For example, it is more advantageous in terms of the effect of reducing the particle size of debris by UV irradiation if ΔD90-10 [4 min] calculated by the following formula is 50 μm or more. D90-10[4 minutes]=(D90[0 minutes]-D10[0 minutes])-(D90[4 minutes]-D10[4 minutes]) Here, D10[0 min] and D90[0 min] are the D10 and D90 particle sizes of the debris obtained by conditioning before the UV irradiation, and D10[4 min] and D90[4 min] are the D10 and D90 particle sizes of the debris obtained when irradiated with UV light for 4 minutes after the conditioning.
[0094] Specifically, the ΔD90-10[4min] may be 50 μm or more, 70 μm or more, 100 μm or more, or 120 μm or more, and may be 300 μm or less, 250 μm or less, 200 μm or less, or 150 μm or less. More specifically, the ΔD90-10[4min] may be 50 μm to 300 μm, 100 μm to 200 μm, or 100 μm to 150 μm.
[0095] In the formula (3), (D90[0 min]-D10[0 min]) may be 80 μm or more, 100 μm or more, 120 μm or more, or 140 μm or more, and may be 220 μm or less, 200 μm or less, or 180 μm or less. Specifically, (D90[0 min]-D10[0 min]) may be 100 μm to 200 μm or 140 μm to 180 μm.
[0096] In the formula (3), (D90[4 min]-D10[4 min]) may be 10 μm or more, 20 μm or more, or 30 μm or more, and may be 80 μm or less, 70 μm or less, 60 μm or less, or 50 μm or less. Specifically, (D90[4 min]-D10[4 min]) may be 20 μm to 60 μm or 30 μm to 50 μm.
[0097] Moreover, the polishing pad according to the above embodiment has various excellent characteristics. For example, when a silicon oxide film of a silicon wafer is polished with a ceria slurry using the polishing pad while irradiating UV light having a wavelength of 100 nm to 380 nm with an intensity of 1 kW from a distance of 5 cm, the polishing rate can be 1700 Å / min or more, 1800 Å / min or more, 1900 Å / min or more, or 2000 Å / min or more, and can be 2600 Å / min or less, 2400 Å / min or less, 2300 Å / min or less, 2200 Å / min or less, or 2100 Å / min or less.
[0098] As a specific example, when a silicon oxide film of a silicon wafer is polished with a ceria slurry using the polishing pad while irradiating UV light having a wavelength of 100 nm to 380 nm with an intensity of 1 kW from a distance of 5 cm, the polishing rate according to the following mathematical formula 1 may be 1800 Å / min to 2200 Å / min. [Number 1] Polishing rate (Å / min) = change in film thickness before and after polishing (Å) / polishing time (min)
[0099] Specifically, the polishing rate may be a polishing rate for a silicon wafer having a diameter of 300 mm on which silicon oxide is deposited. The polishing rate may be measured under conditions of a polishing load of 4.0 psi, a polishing pad rotation speed of 150 rpm, and a calcined ceria slurry being fed at 250 mL / min while rotating a platen at 150 rpm for 60 seconds. The temperature condition during the measurement of the polishing rate is not particularly limited, and may be, for example, a room temperature condition.
[0100] The polishing pad may have a pad wear rate (PWR) of 15 μm / hr to 40 μm / hr when tested at a conditioning pressure of 6 lbf and a rotation speed of 100 to 110 rpm. Specifically, the pad wear rate of the polishing layer may be 15 μm / hr to 35 μm / hr, 15 μm / hr to 30 μm / hr, 20 μm / hr to 40 μm / hr, or 15 μm / hr to 22 μm / hr.
[0101] The thickness of the polishing pad may be 0.8 mm to 5.0 mm, 1.0 mm to 4.0 mm, 1.0 mm to 3.0 mm, 1.5 mm to 2.5 mm, 1.7 mm to 2.3 mm, or 2.0 mm to 2.1 mm. When the thickness is within the above range, the particle size deviation between the upper and lower parts of the pores is minimized, and the basic physical properties of the polishing pad can be sufficiently exhibited.
[0102] [Polishing layer] The polishing layer provides a polishing surface that contacts a semiconductor substrate during a CMP process, and constitutes a top pad of a polishing pad.
[0103] According to one implementation, the polishing layer includes a polyurethane resin. The polishing layer includes a urethane-based prepolymer, a foaming agent, and a curing agent. Specifically, the polyurethane resin is obtained from a composition including a urethane-based prepolymer, a foaming agent, and a curing agent.
[0104] Specifically, the polishing layer includes a polyurethane resin that is a reaction product of a urethane prepolymer, a foaming agent, and a curing agent, i.e., a cured product of a composition in which the above components are mixed, and more specifically, includes a porous polyurethane resin. The polishing layer may also include a plurality of pores formed from the foaming agent.
[0105] The thickness of the polishing layer may be, for example, 0.8 mm or more, 1 mm or more, 1.2 mm or more, or 1.5 mm or more, and 5 mm or less, 3 mm or less, 2.5 mm or less, or 2 mm or less. As a specific example, the thickness of the polishing layer may be 0.8 mm to 5 mm, or 1.5 mm to 3 mm.
[0106] The specific gravity of the polishing layer is, for example, 0.6 g / cm 3 More than 0.7g / cm 3 or more than 0.75g / cm 3 More than 0.9g / cm 3 Below, 0.85g / cm 3 or less than 0.8g / cm 3In one specific example, the specific gravity of the polishing layer may be 0.6 g / cm 3 ~0.9g / cm 3 or 0.7 g / cm 3 ~0.9g / cm 3 It could be.
[0107] The hardness of the polishing layer may be, for example, 30 Shore D or more, 40 Shore D or more, or 50 Shore D or more, and 80 Shore D or less, 70 Shore D or less, 65 Shore D or less, or 60 Shore D or less. As a specific example, the hardness of the polishing layer may be 30 Shore D to 80 Shore D, or 50 Shore D to 65 Shore D.
[0108] The tensile strength of the polishing layer is, for example, 5 N / mm 2 More than 10N / mm 2 or more than 15N / mm 2 Above 30N / mm 2 Below, 25N / mm 2 or less than 20N / mm 2 As a specific example, the tensile strength of the polishing layer may be 5 N / mm 2 ~30N / mm 2 or 15N / mm 2 ~25N / mm 2 It could be.
[0109] The elongation of the polishing layer may be, for example, 50% or more, 70% or more, 90% or more, 106% or more, or 120% or more, and 300% or less, 250% or less, 200% or less, or 150% or less. As a specific example, the elongation of the polishing layer may be 50% to 300% or 90% to 130%. The elongation may be the breaking elongation.
[0110] As a specific example, the abrasive layer has a hardness of 50 Shore D to 65 Shore D and a surface roughness of 15 N / mm 2 ~25N / mm 2 and an elongation of 90% to 130%.
[0111] The pores are present in a dispersed state within the polishing layer. The average diameter of the pores can be, for example, 10 μm to 60 μm, 10 μm to 50 μm, 20 μm to 50 μm, 20 μm to 40 μm, 10 μm to 30 μm, 20 μm to 25 μm, or 30 μm to 50 μm.
[0112] The total area of the pores may be 30% to 60%, 35% to 50%, or 35% to 43% of the total area of the polishing layer, and the total volume of the pores may be 30% to 70%, or 40% to 60% of the total volume of the polishing layer.
[0113] The polishing layer may have grooves for mechanical polishing on the surface thereof. The grooves may have a depth, width and interval appropriate for mechanical polishing, and are not particularly limited.
[0114] In one embodiment of the polishing pad, the polishing layer has a chlorine (Cl) content of 10,000 ppm or less when analyzed according to the IEC 62321-3-2 standard.
[0115] Specifically, the chlorine content can be measured by measuring the chlorine content in a sample according to IEC62321-3-2, an international standard for measuring specific substances in a polymer by combustion-ion chromatography (C-IC). In this case, the sample for measuring the chlorine content can be a circular sample with a diameter of 3 cm and a height of 0.3 cm taken from the polishing layer of the polishing pad.
[0116] The IEC62321-3-2 standard is a halogen component screening test method developed to comply with regulations on halogen use. This test method is more precise / accurate and reproducible than conventional halogen analysis methods (e.g., oxygen bomb-IC, oxygen flask-IC), and is automated, so the test results are more reliable. According to one embodiment, a method for measuring the chlorine content of a polishing pad is to first put a sample containing organic chlorine (C-Cl) components into a combustion tube, burn it in an electric furnace, and then send the resulting material to an adsorption tube to detect chlorine ions (Cl - ) will be measured by ion chromatography.
[0117] In the polishing pad according to the embodiment, the chlorine content in the polishing layer is 10,000 ppm or less, for example, 5,000 ppm or less, 1,000 ppm or less, 500 ppm or less, 200 ppm or less, 100 ppm or less, 80 ppm or less, or 50 ppm or less. By adjusting the chlorine content within the above range, the size of debris can be reduced while maintaining the various physical properties and performance of the polishing pad in an excellent state, thereby minimizing the occurrence of defects and scratches during the CMP process.
[0118] Furthermore, the lower limit of the chlorine content range in the polishing layer according to the above embodiment may be, for example, 0 ppm or more, more than 0 ppm, 1 ppm or more, 5 ppm or more, 10 ppm or more, 20 ppm or more, 50 ppm or more, or 100 ppm or more. Within the above preferred range, debris will aggregate to an appropriate size, the surface area and the adsorption force will be adjusted, the adsorption and desorption on the wafer and the pad will be easy, and the electrical attraction / chucking force will be adjusted, resulting in more appropriate polishing performance.
[0119] As a specific example, the chlorine (Cl) content of the polishing layer analyzed according to the IEC 62321-3-2 standard may be 10 ppm to 1000 ppm. As another specific example, the chlorine (Cl) content of the polishing layer analyzed according to the IEC 62321-3-2 standard may be 10 ppm to 100 ppm, 20 ppm to 80 ppm, or 20 ppm to 50 ppm. As yet another specific example, the chlorine (Cl) content of the polishing layer analyzed according to the IEC 62321-3-2 standard may be 50 ppm to 10000 ppm, or 100 ppm to 10000 ppm.
[0120] In this manner, the polishing pad according to the above embodiment can reduce the size of debris by adjusting the chlorine content within a specific range, thereby minimizing the occurrence of defects and scratches during the CMP process.
[0121] [Urethane prepolymer] The polishing pad according to one implementation includes a urethane-based prepolymer. A prepolymer is a polymer having a relatively low molecular weight whose polymerization degree is stopped at an intermediate stage in order to facilitate molding in the production of a cured product. A prepolymer can be molded into a final cured product by itself or after reacting with other polymerizable compounds.
[0122] In one implementation, the urethane-based prepolymer can be prepared by reacting an isocyanate compound with a polyol.
[0123] The isocyanate compound used in the preparation of the urethane-based prepolymer may be one selected from the group consisting of aromatic diisocyanates, aliphatic diisocyanates, alicyclic diisocyanates, and combinations thereof.
[0124] The isocyanate compound may include, for example, one selected from the group consisting of toluene 2,4-diisocyanate (2,4-TDI), toluene 2,6-diisocyanate (2,6-TDI), naphthalene-1,5-diisocyanate, para-phenylene diisocyanate, tolidine diisocyanate, 4,4'-diphenylmethane diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, and combinations thereof.
[0125] The polyol is a compound containing at least two hydroxyl groups (—OH) per molecule, and may include, for example, one selected from the group consisting of polyether polyols, polyester polyols, polycarbonate polyols, polycaprolactone polyols, and combinations thereof.
[0126] The polyol may include, for example, one selected from the group consisting of polytetramethylene ether glycol, polypropylene ether glycol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,3-butanediol, 2-methyl-1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, tripropylene glycol, and combinations thereof.
[0127] The polyol may have a weight average molecular weight (Mw) of 100 to 3000. The polyol may have a weight average molecular weight (Mw) of, for example, 100 to 3000, for example, 100 to 2000, for example, 100 to 1800.
[0128] In one embodiment, the polyol may include a low molecular weight polyol having a weight average molecular weight (Mw) of 100-300 and a high molecular weight polyol having a weight average molecular weight (Mw) of 300-1800.
[0129] The urethane-based prepolymer may have a weight average molecular weight of 500 to 3000. The urethane-based prepolymer may have a weight average molecular weight (Mw) of, for example, 1000 to 2000, for example, 1000 to 1500.
[0130] In one embodiment, the isocyanate compound for preparing the urethane-based prepolymer includes an aromatic diisocyanate compound, and the aromatic diisocyanate compound can include, for example, 2,4-toluene diisocyanate (2,4-TDI) and 2,6-toluene diisocyanate (2,6-TDI).The polyol compound for preparing the urethane-based prepolymer can include polytetramethylene ether glycol (PTMEG) and diethylene glycol (DEG).
[0131] In another embodiment, the isocyanate compound for preparing the urethane-based prepolymer can include an aromatic diisocyanate compound and an alicyclic diisocyanate compound, for example, the aromatic diisocyanate compound can include 2,4-toluene diisocyanate (2,4-TDI) and 2,6-toluene diisocyanate (2,6-TDI), and the alicyclic diisocyanate compound can include dicyclohexylmethane diisocyanate (H12MDI).The polyol compound for preparing the urethane-based prepolymer can include polytetramethylene ether glycol (PTMEG) and diethylene glycol (DEG).
[0132] The urethane-based prepolymer may have an isocyanate terminal group content (NCO%) of 5% by weight or more, 8% by weight or more, or 10% by weight or more, and 13% by weight or less, 12% by weight or less, or 11% by weight or less. As a specific example, the urethane-based prepolymer may have an isocyanate terminal group content (NCO%) of 10% by weight to 11% by weight.
[0133] The isocyanate terminal group content (NCO%) of the urethane prepolymer can be designed by comprehensively adjusting the types and contents of the isocyanate compound and polyol compound for preparing the urethane prepolymer, process conditions such as temperature, pressure, and time in the process for preparing the urethane prepolymer, and the types and contents of additives used in the preparation of the urethane prepolymer.
[0134] When the isocyanate terminal group content (NCO%) of the urethane prepolymer satisfies the above range, the reaction rate, reaction time, and final cured structure when the urethane prepolymer is subsequently reacted with a curing agent can be adjusted in a direction favorable to the polishing performance depending on the application and purpose of the final polishing pad.
[0135] In one embodiment, the isocyanate end group content (NCO%) of the urethane-based prepolymer may be 8% by weight to 10% by weight, for example, 8% by weight to 9.4% by weight. If the NCO% is less than the above range, the electrical characteristics based on the chemically cured structure in the polishing pad may be realized in such a way that the desired polishing performance cannot be achieved in terms of polishing rate and flatness, and there may be a problem of shortening the life of the polishing pad due to an excessive increase in cutting rate or wear rate. On the other hand, if the NCO% exceeds the above range, surface defects such as scratches and chatter marks on the semiconductor substrate may increase.
[0136] [Foaming agent] The foaming agent may include one selected from the group consisting of a solid-phase foaming agent, a gas-phase foaming agent, a liquid-phase foaming agent, and combinations thereof, as a component for forming a pore structure in the polishing layer.
[0137] According to one embodiment, the foaming agent is a non-chlorine foaming agent that does not contain a chlorine component, and in particular, does not contain or minimizes the use of a chlorine foaming agent component that is commonly used in polishing pad manufacturing, such as vinylidene chloride (VDC). For example, the content of the non-chlorine foaming agent based on the total weight of the foaming agent is 50 wt% or more, 80 wt% or more, 90 wt% or more, 95 wt% or more, 97 wt% or more, 99 wt% or more, or 99.5 wt% or more, and 100 wt% or less or 99.5 wt% or less, and specific examples include 80 wt% to 100 wt%, 90 wt% to 100 wt%, or 80 wt% to 99.5 wt%. The content of the chlorine-based blowing agent based on the total weight of the blowing agent is 20% by weight or less, 10% by weight or less, 5% by weight or less, 1% by weight or less, or 0.5% by weight or less, 0.3% by weight or less, or 0% by weight or more, 0.1% by weight or more, 0.5% by weight or more, and specific examples thereof may be 0 to 20% by weight, 0 to 1% by weight, 0 to 0.5% by weight, or 0.5 to 20% by weight.
[0138] The foaming agent may be one or more selected from a solid-phase foaming agent containing particles having a hollow structure, a liquid-phase foaming agent using a volatile liquid, and an inert gas.
[0139] For example, the solid foaming agent may include particles having a hollow structure, the size of which is adjusted by expanding with heat. Such a solid foaming agent is added to the raw material in an already expanded form and has a uniform particle size, which is advantageous in that the particle size of the pores can be uniformly adjusted.
[0140] The solid-phase foaming agent may also include expandable particles. The expandable particles are particles that have the property of being expandable by heat or pressure, etc., and the size of the expandable particles in the final polishing layer may be determined by the heat or pressure applied during the manufacturing process of the polishing layer. The expandable particles are added to the raw material in a pre-unexpanded particle state, and are expanded by the heat or pressure applied during the manufacturing process of the polishing layer, so that the final size of the expandable particles may be determined.
[0141] The average particle diameter of the solid-phase foaming agent may be, for example, 5 μm to 100 μm, specifically 5 μm to 50 μm or 20 μm to 50 μm. The average particle diameter of the solid-phase foaming agent means the average particle diameter of the expanded particles themselves when the solid-phase foaming agent is particles added to the raw material in an expanded state as described below, and may mean the average particle diameter of the particles after expansion by heat or pressure during the manufacturing process when the solid-phase foaming agent is particles added to the raw material in an unexpanded state as described below.
[0142] The expandable particle type solid-phase foaming agent may include an outer shell made of a resin material and an expansion-inducing component present inside the shell. Such expandable particles may be formed into a hollow structure by vaporizing the internal expansion-inducing component due to heat during the manufacturing process.
[0143] For example, the outer shell may include a thermoplastic resin, which may be one or more selected from the group consisting of an acrylonitrile-based copolymer, a methacrylonitrile-based copolymer, and an acrylic-based copolymer.
[0144] The thickness of the skin is, for example, 0.1 μm or more, 0.5 μm or more, 1 μm or more, 2 μm or more, or 3 μm or more, and 15 μm or less, 12 μm or less, or 10 μm or less, and as a specific example, it can be 2 μm to 15 μm.
[0145] The expansion-inducing component may include one selected from the group consisting of a hydrocarbon compound, a tetraalkylsilane compound, and a combination thereof. Specifically, the hydrocarbon compound may include one selected from the group consisting of ethane, ethylene, propane, propene, n-butane, isobutene, n-butene, isobutene, n-pentane, isopentane, neopentane, n-hexane, heptane, petroleum ether, and a combination thereof. The tetraalkylsilane compound may include one selected from the group consisting of tetramethylsilane, trimethylethylsilane, trimethylisopropylsilane, trimethyl-n-propylsilane, and a combination thereof.
[0146] The solid-phase blowing agent may include inorganic component-treated particles. In one implementation, the solid-phase blowing agent has a surface with silica (SiO 2 The inorganic component treatment of the solid-phase blowing agent may prevent agglomeration between a plurality of particles. The inorganic component-treated solid-phase blowing agent may have different chemical, electrical and / or physical properties on the surface of the blowing agent from those of a solid-phase blowing agent that is not treated with an inorganic component.
[0147] Commercially available solid phase blowing agents include 920DE20d70, 051DET40d25, 051DET40d42 and the like manufactured by Nouryon, and F-65DE, F-80DE, FN-80SDE and the like manufactured by Matsumoto.
[0148] As a specific example, the foaming agent used in the polishing pad according to the above embodiment includes a solid-phase foaming agent, and the solid-phase foaming agent may include one or more selected from the group consisting of acrylonitrile-based copolymers, methyl methacrylate-based copolymers, methacrylonitrile-based copolymers, and acrylic-based copolymers.
[0149] The content of the solid-phase blowing agent may be 0.1 parts by weight or more, 0.5 parts by weight or more, or 1 part by weight or more, and 5 parts by weight or less, 3 parts by weight or less, or 2 parts by weight or less, based on 100 parts by weight of the urethane-based prepolymer. As a specific example, the content of the solid-phase blowing agent may be 0.1 to 5 parts by weight or 0.5 to 2 parts by weight, based on 100 parts by weight of the urethane-based prepolymer.
[0150] The type and content of the solid-phase foaming agent can be designed depending on the desired pore structure and physical properties of the polishing layer.
[0151] Meanwhile, the liquid foaming agent is added during the process of mixing and reacting the prepolymer and the curing agent to form pores, but is not involved in the reaction between the prepolymer and the curing agent. Also, the liquid foaming agent is physically vaporized by heat generated during the process of mixing and reacting the prepolymer and the curing agent to form pores.
[0152] The volatile liquid phase blowing agent does not react with isocyanate groups, amide groups, and alcohol groups, and may be in a liquid phase at 25° C. Specifically, the volatile liquid phase blowing agent may be selected from the group consisting of perfluoro compounds such as cyclopentane, n-pentane, cyclohexane, n-butyl acetate, bis(nonafluorobutyl)(trifluoromethyl)amine, perfluorotributylamine, perfluoro-N-methylmorpholine, perfluorotripentylamine, and perfluorohexane. Commercially available perfluoro compounds include FC-40, FC-43, FC-70, FC-72, FC-770, FC-3283, and FC-3284 from 3M.
[0153] In addition, the blowing agent may include a gas phase blowing agent. For example, the blowing agent may include a solid phase blowing agent and a gas phase blowing agent.
[0154] The gas-phase blowing agent may include an inert gas, and may be used as a pore-forming agent by being added during the reaction of the urethane-based prepolymer with the curing agent.
[0155] The inert gas is not particularly limited as long as it is a gas that does not participate in the reaction between the urethane prepolymer and the curing agent. For example, the inert gas may be nitrogen gas (N 2 ), carbon dioxide gas (CO 2 ), argon gas (Ar), helium gas (He), and combinations thereof.
[0156] The type and content of the gas-phase foaming agent can be designed depending on the desired pore structure and physical properties of the polishing layer.
[0157] The inert gas may be added in a volume equivalent to 10% to 30% of the total volume of the composition. Specifically, the inert gas may be added in a volume equivalent to 15% to 30% of the total volume of the composition. Specifically, the gas-phase blowing agent may be injected through a predetermined injection line during the process of mixing the urethane-based prepolymer, the solid-phase blowing agent, and the curing agent. The injection rate of the gas-phase blowing agent may be about 0.8 L / min to about 2.0 L / min, for example, about 0.8 L / min to about 1.8 L / min, for example, about 0.8 L / min to about 1.7 L / min, for example, about 1.0 L / min to about 2.0 L / min, for example, about 1.0 L / min to about 1.8 L / min, for example, about 1.0 L / min to about 1.7 L / min.
[0158] [Hardening agent] The curing agent is a compound that chemically reacts with the urethane-based prepolymer to form a final cured structure in the polishing layer, and may include, for example, an amine compound or an alcohol compound. Specifically, the curing agent may include one selected from the group consisting of aromatic amines, aliphatic amines, aromatic alcohols, aliphatic alcohols, and combinations thereof.
[0159] According to one embodiment, the curing agent may include a non-chlorine curing agent that does not contain a chlorine component. For example, the content of the non-chlorine curing agent based on the total weight of the curing agent may be 50% by weight or more, 80% by weight or more, 90% by weight or more, 95% by weight or more, 97% by weight or more, 99% by weight or more, or 99.5% by weight or more, and may be 100% by weight or less or 99.5% by weight or less, and may be 80% by weight to 100% by weight, 90% by weight to 100% by weight, or 80% by weight to 99.5% by weight, for example. The content of the chlorine-based curing agent based on the total weight of the curing agent is 20% by weight or less, 10% by weight or less, 5% by weight or less, 1% by weight or less, or 0.5% by weight or less, 0.3% by weight or less, or 0% by weight or more, 0.1% by weight or more, 0.5% by weight or more, and specific examples thereof may be 0% by weight to 20% by weight, 0% by weight to 1% by weight, 0% by weight to 0.5% by weight, or 0.5% by weight to 20% by weight.
[0160] The curing agent may be at least one selected from a solid-phase curing agent and a liquid-phase curing agent.
[0161] The solid-phase hardener may contain an active hydrogen group. The solid-phase hardener may contain an amine group (-NH 2 ).
[0162] In addition, the solid-phase hardener may be an ester compound having two or more benzene rings. Specifically, the solid-phase hardener may contain two or more ester groups in the molecule.
[0163] The solid-phase curing agent may have a weight average molecular weight of 150 to 400, for example, 150 to 350, for example, 200 to 350, for example, 250 to 350, for example, 300 to 350. The solid-phase curing agent may have a melting point (mp) of 100°C to 150°C, for example, 100°C to 140°C, for example, 110°C to 130°C.
[0164] In one implementation, the solid-phase curing agent may include one or more selected from the group consisting of 1,3-propanediol bis(4-aminobenzoate) (PDPAB), 4-(4-aminobenzoyl)oxyphenyl 4-aminobenzoate, 4-(4-aminobenzoyl)oxybutyl 4-aminobenzoate, 4-[4-(4-aminobenzoyl)oxy-3-methylbutoxy]butyl 4-aminobenzoate, and methylene bis-methylanthranilate (MBNA).
[0165] The liquid phase curing agent may contain an active hydrogen group. The liquid phase curing agent may contain an amine group (-NH 2 ), a hydroxyl group (-OH), a carboxylic acid group (-COOH), an epoxy group, and combinations thereof. Specifically, the amine group (-NH 2 ) groups.
[0166] The liquid phase curing agent may contain sulfur in the molecule, specifically, may contain two or more sulfur elements in the molecule.
[0167] The liquid phase curing agent has a weight average molecular weight of 50-300, for example, 100-250, for example, 150-250, for example, 200-250.
[0168] The liquid-phase hardener may be in a liquid phase at room temperature, or may have a boiling point (bp) of 160°C to 240°C, specifically 170°C to 240°C, more specifically 170°C to 220°C.
[0169] Examples of the liquid phase curing agent may include one or more selected from the group consisting of 3,5-dimethylthio-2,6-diaminotoluene (DMTDA), 2,6-bis(methylthio)-4-methyl-1,3-benzenediamine, and N,N'-bis(sec-butylamino)diphenylmethane.
[0170] In addition, the curing agent may further include other curing agents in addition to the liquid-phase curing agent and the solid-phase curing agent. The other curing agents may be, for example, one or more of an amine compound and an alcohol compound. Specifically, the other curing agents may include one or more compounds selected from the group consisting of aromatic amines, aliphatic amines, aromatic alcohols, and aliphatic alcohols.
[0171] For example, the other curing agent may be one or more selected from the group consisting of diaminodiphenyl methane, diaminodiphenyl sulphone, m-xylylene diamine, isophoronediamine, ethylenediamine, diethylenetriamine, triethylenetetramine, polypropylenediamine, polypropylenetriamine, ethylene glycol, diethyleneglycol, dipropyleneglycol, butanediol, hexanediol, glycerine, and trimethylolpropane.
[0172] As a specific example, the curing agent may include one or more selected from the group consisting of diethyltoluenediamine (DETDA), 3,5-dimethylthio-2,6-diaminotoluene (DMTDA), 1,3-propanediol bis(4-aminobenzoate) (PDPAB), N,N'-bis(sec-butylamino)diphenylmethane, 2,6-bis(methylthio)-4-methyl-1,3-benzenediamine, 4-(4-aminobenzoyl)oxyphenyl 4-aminobenzoate, 4-(4-aminobenzoyl)oxybutyl 4-aminobenzoate, 4-[4-(4-aminobenzoyl)oxy-3-methylbutoxy]butyl 4-aminobenzoate, and methylene bis-methylanthranilate (MBNA).
[0173] The content of the curing agent may be 5 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, or 20 parts by weight or more, and 50 parts by weight or less, 45 parts by weight or less, 40 parts by weight or less, 35 parts by weight or less, 30 parts by weight or less, or 25 parts by weight or less, based on 100 parts by weight of the urethane-based prepolymer. Specifically, the content of the curing agent may be 10 parts by weight to 40 parts by weight, more specifically, 15 parts by weight to 35 parts by weight or 15 parts by weight to 25 parts by weight, based on 100 parts by weight of the urethane-based prepolymer.
[0174] [Additives] The composition for preparing the polishing layer may further include other additives such as a surfactant, a reaction rate modifier, etc. The names "surfactant", "reaction rate modifier", etc. are arbitrary names based on the main role of the corresponding substance, and each corresponding substance does not necessarily perform only the function limited to the role of the corresponding name.
[0175] The surfactant is not particularly limited as long as it is a substance that serves to prevent phenomena such as pore aggregation or overlapping, etc. For example, the surfactant may include a silicone-based surfactant.
[0176] The surfactant may be used in an amount of 0.2 to 2 parts by weight based on 100 parts by weight of the urethane-based prepolymer. Specifically, the surfactant may be used in an amount of 0.2 to 1.9 parts by weight, for example, 0.2 to 1.8 parts by weight, for example, 0.2 to 1.7 parts by weight, for example, 0.2 to 1.6 parts by weight, for example, 0.2 to 1.5 parts by weight, for example, 0.5 to 1.5 parts by weight based on 100 parts by weight of the urethane-based prepolymer. When the surfactant is included in an amount within the above range, pores derived from the gas phase blowing agent can be stably formed and maintained in the mold.
[0177] The reaction rate regulator plays a role of accelerating or retarding the reaction, and may be a reaction promoter, a reaction retarder, or both, depending on the purpose. The reaction rate regulator may include a reaction promoter. For example, the reaction promoter may be one or more reaction promoters selected from the group consisting of tertiary amine compounds and organometallic compounds.
[0178] Specifically, the reaction rate regulator may include one or more selected from the group consisting of triethylenediamine, dimethylethanolamine, tetramethylbutanediamine, 2-methyl-triethylenediamine, dimethylcyclohexylamine, triethylamine, triisopropanolamine, 1,4-diazabicyclo(2,2,2)octane, bis(2-methylaminoethyl)ether, trimethylaminoethylethanolamine, N,N,N,N,N″-pentamethyldiethylenetriamine, dimethylaminoethylamine, dimethylaminopropylamine, benzyldimethylamine, N-ethylmorpholine, N,N-dimethylaminoethylmorpholine, N,N-dimethylcyclohexylamine, 2-methyl-2-azanorbornene, dibutyltin dilaurate, stannous octoate, dibutyltin diacetate, dioctyltin diacetate, dibutyltin maleate, dibutyltin di-2-ethylhexanoate, and dibutyltin dimercaptide. Specifically, the reaction rate regulator may include one or more selected from the group consisting of benzyldimethylamine, N,N-dimethylcyclohexylamine, and triethylamine.
[0179] The reaction rate adjuster may be used in an amount of 0.05 parts by weight to 2 parts by weight based on 100 parts by weight of the urethane-based prepolymer. Specifically, the reaction rate adjuster may be used in an amount of 0.05 parts by weight to 1.8 parts by weight, for example, 0.05 parts by weight to 1.7 parts by weight, for example, 0.05 parts by weight to 1.6 parts by weight, for example, 0.1 parts by weight to 1.5 parts by weight, for example, 0.1 parts by weight to 1.3 parts by weight, for example, 0.2 parts by weight to 1.8 parts by weight, for example, 0.2 parts by weight to 1.7 parts by weight, for example, 0.2 parts by weight to 1.6 parts by weight, for example, 0.2 parts by weight to 1.5 parts by weight, for example, 0.5 parts by weight to 1 part by weight based on 100 parts by weight of the urethane-based prepolymer. When the reaction rate adjuster is used in the above content range, the curing reaction rate of the prepolymer composition can be appropriately adjusted to form a polishing layer having pores of a desired size and hardness.
[0180] [Support layer] The support layer constitutes a sub pad and serves to absorb and disperse external impacts applied to the polishing layer while supporting the polishing layer, thereby minimizing damage and defects to an object to be polished during a polishing process using the polishing pad.
[0181] The support layer may include, but is not limited to, a nonwoven fabric or suede. In one embodiment, the support layer may be a resin-impregnated nonwoven fabric. The nonwoven fabric may be a fibrous nonwoven fabric comprising one selected from the group consisting of polyester fibers, polyamide fibers, polypropylene fibers, polyethylene fibers, and combinations thereof.
[0182] The resin impregnated into the nonwoven fabric may include one selected from the group consisting of polyurethane resin, polybutadiene resin, styrene-butadiene copolymer resin, styrene-butadiene-styrene copolymer resin, acrylonitrile-butadiene copolymer resin, styrene-ethylene-butadiene-styrene copolymer resin, silicone rubber resin, polyester-based elastomer resin, polyamide-based elastomer resin, and combinations thereof.
[0183] The thickness of the support layer may be, for example, 0.3 mm or more, or 0.5 mm or more, and 3 mm or less, 2 mm or less, or 1 mm or less. As a specific example, the thickness of the support layer may be 0.3 mm to 3 mm, or 0.5 mm to 1 mm.
[0184] The hardness of the support layer may be, for example, 50 Asker C or more, 60 Asker C or more, or 70 Asker C or more, and 100 Asker C or less, 90 Asker C or less, or 80 Asker C or less. As a specific example, the hardness of the support layer may be 50 Asker C to 100 Asker C or 60 Asker C to 90 Asker C.
[0185] Also, an adhesive layer may be inserted between the polishing layer (upper pad) and the support layer (lower pad).
[0186] The adhesive layer may include a hot melt adhesive. The hot melt adhesive may be one or more selected from the group consisting of polyurethane resins, polyester resins, ethylene-vinyl acetate resins, polyamide resins, and polyolefin resins. Specifically, the hot melt adhesive may be one or more selected from the group consisting of polyurethane resins and polyester resins.
[0187] In addition, a double-sided tape is attached to the lower part of the support layer, and when the double-sided tape is applied to a CMP device, the release paper of the double-sided tape can be removed and the double-sided tape can be attached to a platen for use.
[0188] [Polishing pad manufacturing method] A method for manufacturing a polishing pad according to one embodiment includes preparing a polishing pad composition including a urethane-based prepolymer, a foaming agent, and a curing agent, injecting the polishing pad composition into a mold and curing it to produce a polishing layer, and bonding the polishing layer to a support layer.
[0189] The specific types and contents of the urethane-based prepolymer, the curing agent, and the foaming agent are as exemplified above.
[0190] As a specific example, the foaming agent includes a solid-phase foaming agent, and the solid-phase foaming agent includes at least one selected from the group consisting of an acrylonitrile-based copolymer, a methyl methacrylate-based copolymer, a methacrylonitrile-based copolymer, and an acrylic-based copolymer. The curing agent may include at least one selected from the group consisting of diethyltoluenediamine (DETDA), 3,5-dimethylthio-2,6-diaminotoluene (DMTDA), 1,3-propanediol bis(4-aminobenzoate) (PDPAB), N,N'-bis(sec-butylamino)diphenylmethane, 2,6-bis(methylthio)-4-methyl-1,3-benzenediamine, 4-(4-aminobenzoyl)oxyphenyl 4-aminobenzoate, 4-(4-aminobenzoyl)oxybutyl 4-aminobenzoate, 4-[4-(4-aminobenzoyl)oxy-3-methylbutoxy]butyl 4-aminobenzoate, and methylene bis-methylanthranilate (MBNA).
[0191] The polishing pad composition may be prepared by sequentially or simultaneously mixing the urethane-based prepolymer, the foaming agent, and the curing agent.
[0192] As an example, the step of preparing the polishing pad composition may be performed by mixing a urethane-based prepolymer with a curing agent and then further mixing it with a foaming agent, or by mixing the urethane-based prepolymer with the foaming agent and then further mixing it with the curing agent.
[0193] As another example, the urethane-based prepolymer, the curing agent, and the blowing agent are added to the mixing process at substantially the same time, and when a blowing agent, a surfactant, and an inert gas are further added, they may also be added to the mixing process at substantially the same time.
[0194] As another example, the urethane prepolymer, the blowing agent and the surfactant may be premixed and then the curing agent may be added, or the curing agent and the inert gas may be added together.
[0195] In the mixing, the urethane prepolymer and the curing agent are mixed to start the reaction, and the foaming agent and the inert gas are uniformly dispersed in the raw material. In this case, the reaction rate regulator can be intervened in the reaction between the urethane prepolymer and the curing agent from the early stage of the reaction to adjust the reaction rate. Specifically, the mixing can be performed at a speed of 1000 rpm to 10000 rpm or 4000 rpm to 7000 rpm. When the speed is within the above range, it is more advantageous for the inert gas and the foaming agent to be uniformly dispersed in the raw material.
[0196] The step of preparing the polishing pad composition may be carried out at a temperature of 50° C. to 150° C., and may be carried out under vacuum degassing conditions as necessary.
[0197] When the foaming agent includes a solid-phase foaming agent, the step of preparing the polishing pad composition may include a step of preparing a first preliminary composition by mixing the urethane-based prepolymer and the solid-phase foaming agent, and a step of preparing a second preliminary composition by mixing the first preliminary composition and a curing agent.
[0198] The viscosity of the first preliminary composition at about 80° C. may be about 1000 cps to about 2000 cps, for example, about 1000 cps to about 1800 cps, for example, about 1000 cps to about 1600 cps, for example, about 1000 cps to about 1500 cps.
[0199] When the foaming agent includes a gas-phase foaming agent, the step of preparing the polishing pad composition may include the steps of preparing a third preliminary composition including the urethane-based prepolymer and the curing agent, and injecting the gas-phase foaming agent into the third preliminary composition to prepare a fourth preliminary composition. In one implementation, the third preliminary composition may further include a solid-phase foaming agent.
[0200] In one implementation example, the process for manufacturing the polishing layer may include preparing a mold preheated to a first temperature, injecting and curing the polishing pad composition into the preheated mold, and post-curing the hardened polishing pad composition under a second temperature condition higher than the preheat temperature.
[0201] In one embodiment, the temperature difference between the first temperature and the second temperature is about 10° C. to about 40° C., for example, about 10° C. to about 35° C., for example, about 15° C. to about 35° C. In one embodiment, the first temperature is about 60° C. to about 100° C., for example, about 65° C. to about 95° C., for example, about 70° C. to about 90° C. In one embodiment, the second temperature is about 100° C. to about 130° C., for example, about 100° C. to about 125° C., for example, about 100° C. to about 120° C.
[0202] The step of curing the polishing pad composition at the first temperature may be performed for about 5 minutes to about 60 minutes, such as about 5 minutes to about 40 minutes, such as about 5 minutes to about 30 minutes, for example, about 5 minutes to about 25 minutes.
[0203] The step of post-curing the polishing pad composition cured at the first temperature at the second temperature may be carried out for about 5 hours to about 30 hours, for example, about 5 hours to about 25 hours, for example, about 10 hours to about 30 hours, for example, about 10 hours to about 25 hours, for example, about 12 hours to about 24 hours, for example, about 15 hours to about 24 hours.
[0204] Then, the step of injecting the polishing pad composition into the mold and curing it is performed under a temperature condition of 60° C. to 120° C. and a pressure of 50 kg / m 2 ~200kg / m 2 The reaction may be carried out under pressure conditions of 0.1 to 1000 MPa.
[0205] The manufacturing method may further include a step of cutting the surface of the obtained polishing pad, a step of processing grooves in the surface, a step of bonding with a lower layer, a step of inspecting, a step of packaging, etc. These steps may be performed by a normal polishing pad manufacturing method.
[0206] As an example, the method for manufacturing the polishing pad may include processing at least one surface of the polishing layer, which may include at least one of forming grooves on the at least one surface of the polishing layer, turning the at least one surface of the polishing layer, and roughening the at least one surface of the polishing layer.
[0207] The grooves may include at least one of concentric grooves formed at a predetermined interval from the center of the polishing layer and radial grooves continuously connected from the center of the polishing layer to the edge of the polishing layer. The turning may be performed by a method of cutting off a predetermined thickness of the polishing layer using a cutting tool. The roughening may be performed by processing the surface of the polishing layer with a sanding roller.
[0208] [Method of manufacturing semiconductor devices] The polishing pad described above can be used to manufacture semiconductor devices by chemical mechanical polishing. A method for manufacturing a semiconductor device according to one embodiment includes a step of chemically and mechanically polishing a semiconductor substrate using the polishing pad described above, and conditioning a polishing layer of the polishing pad while irradiating the polishing pad with UV light having a wavelength of 100 nm to 380 nm.
[0209] Specifically, the method for manufacturing a semiconductor device includes polishing the surface of the semiconductor substrate by rotating the polishing layer of the polishing pad and the surface of the semiconductor substrate relative to each other so that the polishing layer and the surface of the semiconductor substrate are in contact with each other, and conditioning the polishing layer of the polishing pad while irradiating the polishing layer with UV light having a wavelength of 100 nm to 380 nm.
[0210] 7 and 8 show the configuration of an apparatus for irradiating UV light during CMP according to one embodiment. Referring to FIG. 7 and FIG. 8, in the apparatus according to one embodiment, a UV lamp 700 is installed on a polishing pad 100. The UV lamp can be configured to be adjustable in angle and height. The UV lamp can irradiate light in a wavelength range of 100 nm to 380 nm to the polishing pad. FIG. 2 shows that defects are generated by debris during the manufacturing process of a semiconductor device. Referring to FIG. 2, defects 650 and scratches may occur on the surface of a semiconductor device due to debris 150 generated from the polishing layer. However, the polishing pad according to the embodiment has a characteristic that the particle size of the debris is reduced by irradiating UV light during the CMP process, and thus, by utilizing such a characteristic of the polishing pad, the generation of defects and scratches in the semiconductor device may be minimized by irradiating UV light during the CMP process. As a result, when a semiconductor device is manufactured by the CMP process using the polishing pad according to the embodiment, the CMP performance and yield may be improved.
[0211] A method for manufacturing a semiconductor device according to an embodiment will now be described in detail. First, the polishing pad 100 according to one embodiment is mounted on the platen 200, and then the semiconductor substrate 600 to be polished is placed on the polishing pad 100. At this time, the surface to be polished of the semiconductor substrate 600 directly contacts the polishing surface of the polishing pad 100. For polishing, a CMP slurry 450 may be supplied onto the polishing pad through a slurry supply 400. The flow rate of the CMP slurry 450 supplied through the slurry supply 400 is about 10 cm. 3 / min ~ approx. 1000cm 3 / min. can be selected according to the purpose. For example, about 50 cm 3 / min ~ approx. 500cm 3 / min, but is not limited to this.
[0212] Thereafter, the semiconductor substrate 600 and the polishing pad 100 may rotate relative to each other to polish the surface of the semiconductor substrate 600. At this time, the rotating direction of the semiconductor substrate 600 and the rotating direction of the polishing pad 100 may be the same or opposite to each other. The rotating speeds of the semiconductor substrate 600 and the polishing pad 100 may be selected according to the purpose within a range of about 10 rpm to about 500 rpm, respectively, and may be, for example, about 30 rpm to about 200 rpm, but are not limited thereto.
[0213] The semiconductor substrate 600 may be attached to the polishing head 510 and brought into contact with the polishing surface of the polishing pad 100 under a predetermined load, and then the surface of the semiconductor substrate 600 may be polished. The load applied by the polishing head 510 to the surface of the semiconductor substrate 600 and the polishing surface of the polishing pad 100 is about 1 gf / cm. 2 ~About 1000gf / cm 2 can be selected according to the purpose, for example, about 10 gf / cm 2 ~About 800gf / cm 2 It can be, but is not limited to, these.
[0214] In one embodiment, the semiconductor substrate 600 to be polished may include an oxide film, a tungsten film, or a composite film thereof. Specifically, the semiconductor substrate 600 may include an oxide film, a tungsten film, or a composite film of an oxide film and a tungsten film. The composite film of an oxide film and a tungsten film may be a multi-layer film in which the tungsten film is stacked on one side of the oxide film, or may be a single layer film in which an oxide region and a tungsten region are mixed in one layer. Since the polishing object has such film quality characteristics and the polishing pad has the characteristics according to the embodiment, defects in the semiconductor device manufactured by the manufacturing method of the semiconductor device may be minimized.
[0215] In one embodiment, the method for manufacturing a semiconductor device may further include, in the step of polishing the object to be polished, a step of supplying either one of the oxide film polishing slurry and the tungsten film polishing slurry, or a step of sequentially supplying the oxide film polishing slurry and the tungsten film polishing slurry to a polishing surface.
[0216] For example, when the semiconductor substrate to be polished includes an oxide film, the method for manufacturing a semiconductor device may include a step of supplying the oxide film polishing slurry. When the semiconductor substrate includes a tungsten film, the method for manufacturing a semiconductor device may include a step of supplying the tungsten film polishing slurry. When the semiconductor substrate includes a composite film of an oxide film and a tungsten film, the method for manufacturing a semiconductor device may include a step of supplying the oxide film polishing slurry and the tungsten film polishing slurry sequentially to the polishing surface. At this time, depending on the process, the oxide film polishing slurry may be supplied first and then the tungsten film polishing slurry may be supplied later, or the tungsten film polishing slurry may be supplied first and then the oxide film polishing slurry may be supplied later.
[0217] In one embodiment, the method for manufacturing a semiconductor device further includes a step of processing the polishing surface of the polishing pad 100 with a conditioner 300 simultaneously with polishing the semiconductor substrate 600 in order to maintain the polishing surface of the polishing pad 100 in a state suitable for polishing.
[0218] The method of manufacturing a semiconductor device also includes conditioning the polishing layer of the polishing pad while irradiating the polishing layer with UV light having a wavelength of 100 nm to 380 nm. In one embodiment of the apparatus, a UV lamp 700 is installed on the polishing pad 100. The UV lamp may be configured to be adjustable in angle and height.
[0219] For example, the height of the UV lamp may be 2 cm to 30 cm, specifically 3 cm to 10 cm, and more specifically 3 cm to 7 cm, from the surface of the polishing pad 100.
[0220] Furthermore, the intensity of the UV light on the surface of the polishing pad 100 may be 100W to 2kW, more specifically, 500W to 1.5kW.
[0221] The UV light irradiation time may be 1 minute or more, 2 minutes or more, or 3 minutes or more, and may be 20 minutes or less, 10 minutes or less, 7 minutes or less, 5 minutes or less, or 4 minutes or less. For example, the UV light irradiation time may be 1 minute to 20 minutes, 1 minute to 10 minutes, 2 minutes to 10 minutes, 1 minute to 7 minutes, 1 minute to 5 minutes, or 2 minutes to 5 minutes. As a specific example, the UV light irradiation time may be 2 minutes to 4 minutes.
[0222] (Example) Examples are described below, but the feasible scope is not limited to these.
[0223] A. Polishing Pad Production and Evaluation (Examples A1 to A7 and Comparative Examples A1 and A2: Production of Polishing Pads) Step (1) Preparation of prepolymer Toluene diisocyanate (TDI), dicyclohexylmethane diisocyanate (H12MDI), polytetramethylene ether glycol (PTMEG) and diethylene glycol (DEG) were charged into a four-neck flask and reacted at 80°C for 3 hours to prepare a urethane prepolymer. The NCO% of the prepolymer was measured and is shown in Table 1 below.
[0224] Step (2) Manufacturing the polishing pad A casting machine equipped with tanks and supply lines for supplying raw materials such as prepolymer, hardener, inert gas, and foaming agent was prepared. The urethane prepolymer, foaming agent, hardener, and inert gas (N 2 ), and a silicone surfactant (EVONIK) were filled into each tank. The raw materials were fed into the mixing head at a constant rate through each feeding line while being stirred. The foaming agent and curing agent used were those shown in Table 1 below, and the prepolymer and curing agent were fed in an equivalent ratio of 1:1 at a total rate of 10 kg / min.
[0225] A mold (1000 mm x 1000 mm x 3 mm) was prepared and preheated at 80°C, and the above-mentioned stirred raw material was discharged into the mold and reacted to obtain a solid cake-like molded body. After that, the upper and lower ends of the molded body were cut to obtain a polishing layer for the top pad.
[0226] Thereafter, the polishing layer was subjected to surface milling and groove forming processes, and then attached to a support layer for a sub pad with a hot melt adhesive to produce a polishing pad.
[0227] A double-sided tape (442JS, 3M) was attached to the bottom of the support layer so that it could be attached to the platen of a CMP device.
[0228] The curing agents and foaming agents used in the examples and comparative examples are as follows. - DMTDA: 3,5-dimethylthio-2,6-diaminotoluene, Covestro - MOCA: 4,4'-methylenebis(2-chloroaniline), Ishihara - F-65DE: Acrylonitrile / Methyl Methacrylate / Methacrylonitrile Copolymer, Expanded Cell Type, Matsumoto - F-80DE: Acrylonitrile / Methyl Methacrylate / Methacrylonitrile Copolymer, Expanded Cell Type, Matsumoto - 051DET40d25: Acrylonitrile / Methacrylonitrile Copolymer, Expanded Cell Type, Nouryon - 051DET40d42: Acrylonitrile / Methacrylonitrile Copolymer, Expanded Cell Type, Nouryon - 461DET40d25: Acrylonitrile / Dichloroethane, Expanded Cell Type, Nouryon
[0229] The configurations of the above-mentioned Examples and Comparative Examples are summarized in Table 1 below.
[0230] JPEG2025018957000002.jpg135162
[0231] (Test Example A1) The polishing layer, support layer, and polishing pad formed by laminating these thus produced were subjected to the following tests.
[0232] (1)Hardness The samples were cut into 5 cm x 5 cm (thickness: 2 mm) and stored at room temperature, 30°C, 50°C, and 70°C for 12 hours, respectively, and then the Shore D hardness and Asker C hardness were measured using a hardness tester.
[0233] (2) Specific gravity The sample was cut into a size of 2 cm x 5 cm (thickness: 2 mm) and stored at 25°C for 12 hours, after which the specific gravity was measured using a hydrometer.
[0234] (3) Tensile strength The sample was cut into a size of 4 cm×1 cm (thickness: 2 mm), and the maximum strength value just before the breakage of the polishing pad was measured using a universal testing meter (UTM) at a speed of 50 mm / min.
[0235] (4) Growth rate The sample was cut to 4 cm x 1 cm (thickness: 2 mm), and the maximum deformation just before the abrasive pad broke was measured using a universal testing meter (UTM) at a speed of 50 mm / min. The ratio of the maximum deformation to the initial length was then expressed as a percentage (%). The results are summarized in the table below.
[0236] JPEG2025018957000003.jpg109160
[0237] As can be seen from the above table, the polishing pads of Examples A1 to A7 were at the same or higher levels as the polishing pads of Comparative Examples A1 and A2 in terms of hardness, specific gravity, tensile strength, and elongation.
[0238] (Test Example A2) Each of the polishing pads thus produced was subjected to the following tests.
[0239] (1)Removal rate A silicon wafer having a diameter of 300 mm on which silicon oxide had been deposited by a CVD process was placed in a CMP polishing apparatus, and then the silicon wafer was placed with the silicon oxide film facing down on the platen to which the porous polyurethane polishing pad had been attached.
[0240] Thereafter, the silicon oxide film was polished by rotating the platen at 150 rpm for 60 seconds while feeding the calcined ceria slurry onto the polishing pad at a rate of 250 mL / min under conditions of a polishing load of 4.0 psi and a polishing pad rotation speed of 150 rpm.
[0241] After polishing, the silicon wafer was removed from the carrier, loaded onto a spin dryer, washed with deionized water (DIW), and then dried with nitrogen for 15 seconds. The change in film thickness of the dried silicon wafer before and after polishing was measured using a spectroscopic interference wafer thickness meter (model name: SI-F80R, Keyence Corporation).
[0242] Then, the polishing rate was calculated using the following mathematical formula 1. [Number 1] Polishing rate (Å / min) = change in film thickness before and after polishing (Å) / polishing time (min)
[0243] (2) Defects Using a CMP polishing device, polishing was carried out in the same manner as in the polishing rate test. After polishing, the silicon wafer was moved to a cleaner and washed with 1% HF, 1% H 2 NO 3 The wafers were then washed with deionized water (DIW) for 10 seconds each. They were then transferred to a spin dryer, washed with deionized water (DIW), and dried with nitrogen for 15 seconds. The dried silicon wafers were measured for defect changes before and after polishing using a defect measurement device (model name: XP+, KLA-TENCOR). Specifically, the total number of scratches, chatter marks, pits, and residues on the wafers were measured.
[0244] (3) Chlorine content A circular sample with a diameter of 3 cm and a height of 0.3 cm was prepared from the polishing layer of the polishing pad. The chlorine content in the sample was measured according to IEC 62321-3-2, an international standard for the measurement of specific substances in polymers by combustion ion chromatography (C-IC).
[0245] (4) Debris size (D50 particle size) a) Collection of debris aqueous solution A porous polyurethane polishing pad was attached and set on the platen of a CMP polishing device. After that, the operation of the carrier was removed and debris from the polishing layer was collected using only a conditioner and deionized water (DIW). The platen speed was set to 93 rpm, the conditioner load was 9 lb, the rotation speed was 64 rpm, and the sweep speed was 19 times / min. Conditioning of the polishing layer was performed using a CI45 (pad cutting rate 80-90 μm / hr, Sesol Co., Ltd.) as a conditioner disk while injecting deionized water at 300 cc / min. Debris from the polishing layer generated 10 minutes after conditioning was collected in a solution state mixed with deionized water to obtain 300 mL of debris aqueous solution.
[0246] b) pH adjustment and particle size analysis of debris The debris aqueous solution had a pH level of 6.0 to 6.5, and the pH was adjusted to 5.5 using an aqueous nitric acid solution. The concentration of the aqueous nitric acid solution used was 35%. The D50 particle size of the debris in the debris aqueous solution was obtained using a particle size analyzer (Mastersize 3000, Malvern) and a medium-capacity automatic wet disperser (Hydro MV, Malvern). The analyzer settings were: polyurethane 1.55 as the refractive index of the analyte, deionized water 1.33 as the refractive index of the dispersant, and a stirring speed of 2500 rpm.
[0247] (5) Zeta potential A debris aqueous solution was obtained by the same method as in (4) a) above. For particle stability of the debris aqueous solution, the solution was stored at room temperature for 24 hours to allow particles with a diameter of 20 μm or more to precipitate. Then, the supernatant located within 10 mm from the upper surface of the solution was collected to obtain a sample. The obtained sample had a pH level of 6.0 to 6.5, and the pH was adjusted to 5.5 using an aqueous nitric acid solution. The concentration of the aqueous nitric acid solution used was 35%. The debris concentration in the liquid sample was confirmed to be about 0.01% by weight. The concentration was measured using a heated moisture meter (MX-50, AND Co.) after placing about 5 g of the liquid sample in an aluminum dish. The zeta potential of the sample was measured using a zetasizer (Nano-ZS90, Malvern Co.). Specifically, 1 mL of the sample was placed in a cuvette of the zetasizer, and the measurement was repeated three times to obtain the zeta potential. At this time, the device settings were set to RI 1.550 and absorption 0.010 based on the polyurethane value. The test results are summarized in the table below.
[0248] JPEG2025018957000004.jpg79165
[0249] As can be seen from the table, the polishing pads of Examples A1 to A7 were measured to have a chlorine (Cl) content within a preferred range, and performance such as removal rate was at a level equal to or higher than that of Comparative Examples A1 and A2. In particular, the debris particle size of the polishing pads of Examples A1 to A7 was measured to be smaller than that of Comparative Examples A1 and A2, and the number of defects / scratches was measured to be significantly smaller. Furthermore, the zeta potential of the polishing pads of Examples A1 to A7 was also measured to be within a preferred range.
[0250] (6) Debris size and zeta potential due to pH change For the polishing pads of the examples and comparative examples, the debris particle size (D50[5.5]) at pH 5.5 and the debris particle size (D50
[10] ) at pH 10 were measured by the same method as in (4) above.
[0251] In addition, for the polishing pads of the examples and comparative examples, the zeta potential (Zp[5.5]) of the debris aqueous solution at pH 5.5 and the zeta potential (Zp
[10] ) of the debris aqueous solution at pH 10 were measured using a method similar to that described in (5) above.
[0252] At this time, the pH of the debris aqueous solution was adjusted by adding a nitric acid aqueous solution or a potassium hydroxide aqueous solution. Specifically, when adjusting the initially obtained debris aqueous solution (pH 6.0 to 6.5) to pH 5.5, a nitric acid aqueous solution was added, and when adjusting to pH 10, a potassium hydroxide aqueous solution was added. The concentration of the nitric acid aqueous solution used at this time was 35%, and the concentration of the potassium hydroxide aqueous solution was 10%.
[0253] The debris size and zeta potential thus measured were used to calculate the following equations (1) to (3). D50[5.5] / Zp[5.5]...(1) (D50[5.5] / D50
[10] )×100...(2) Zp[5.5]-Zp
[10] ...(3) Where: D50[5.5] is the D50 particle size (μm) of the debris obtained when conditioning the polishing layer under a pH 5.5 condition, D50
[10] is the D50 particle size (μm) of the debris obtained when conditioning the polishing layer under a pH 10 condition, Zp[5.5] is the zeta potential (mV) of an aqueous solution containing debris obtained during conditioning of the polishing layer at a concentration of 0.01% by weight under a pH of 5.5 condition; Zp
[10] is the zeta potential (mV) of an aqueous solution containing debris obtained during conditioning of the polishing layer at a concentration of 0.01% by weight under a pH of 10 condition.
[0254] The results are summarized in the table below. The results of the above-mentioned defect / scratch test are also shown in the table below. JPEG2025018957000005.jpg109163
[0255] As can be seen from the table, the polishing pads of Examples A1 to A7 had a D50 particle size of debris obtained from the polishing layer of 50 μm or less under pH 5.5 conditions, and the zeta potential of the debris aqueous solution was measured within the range of -20 mV to 30 mV under pH 5.5 conditions. In addition, the polishing pads of Examples A1 to A7 had values measured under other pH conditions and values of formulas (1) to (3) all within the preferred ranges, and as a result, the number of defects / scratches generated on the silicon wafer during the CMP process was as low as less than 20.
[0256] In particular, the polishing pads of Examples A1 to A3 had a D50 particle size of 20 μm or less of debris obtained from the polishing layer under pH 5.5 conditions, and the zeta potential of the debris aqueous solution was measured within the range of 0 mV to 20 mV under pH 5.5 conditions. Furthermore, the polishing pads of Examples A1 to A3 had values measured under other pH conditions and values of formulas (1) to (3) all within the preferred ranges, and as a result, the number of defects / scratches generated on the silicon wafer during the CMP process was very small, less than 10.
[0257] On the other hand, in the polishing pads of Comparative Examples A1 and A2, the zeta potential value of the debris aqueous solution obtained from the polishing layer was measured at less than -20 mV under pH 5.5 conditions, and it was confirmed that other measured values and the values of equations (1) to (3) were also outside the preferred ranges. As a result, the number of defects / scratches generated on the silicon wafer during the CMP process significantly increased to 25 or more.
[0258] B. Polishing pad production and evaluation under UV irradiation (Example B1: Production of polishing pad) Step (1) Preparation of urethane prepolymer 2,4-toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), dicyclohexylmethane diisocyanate (H12MDI), polytetramethylene ether glycol (PTMEG), and diethylene glycol (DEG) were placed in a four-neck flask and reacted at 80°C for 3 hours to produce a urethane prepolymer with a terminal NCO group content (NCO%) of 10% by weight.
[0259] Step (2) Preparation of the polishing layer A casting machine equipped with tanks and supply lines for supplying raw materials such as prepolymer, hardener, inert gas, and foaming agent was prepared. The urethane prepolymer prepared above, hardener (DMTDA), solid-phase foaming agent (F-65DE, Matsumoto Co.), inert gas (N 2 ), and a silicone surfactant (EVONIK) were filled into each tank. Specifically, 32 parts by weight of a curing agent, 1 part by weight of a solid-phase foaming agent, and 1 part by weight of a surfactant were filled relative to 100 parts by weight of the prepolymer, and an inert gas was introduced at a rate of 1.5 L / min.
[0260] The raw materials were stirred while being fed into the mixing head at a constant speed through each feeding line. The rotation speed of the mixing head was about 5000 rpm. The mixed composition of the raw materials was mixed in the mixing head and then poured into a mold having a length of 1000 mm, a width of 1000 mm, and a height of 3 mm. The temperature of the mold was adjusted to about 80 (± 5) °C. The mixed composition was solidified in the mold and cast into a sheet. The sheet was post-cured at about 110 (± 5) °C for about 18 hours to produce an abrasive layer.
[0261] Step (3) Manufacturing the polishing pad One side of the polishing layer was turned using a cutting tool, and grooves were machined using a tip to produce an average thickness of 2 mm. A cushion layer was provided in which a polyester fiber nonwoven fabric was impregnated with polyurethane resin, and a heat-sealing adhesive was applied to one side of the cushion layer and to the back side of the groove-forming surface of the polishing layer. The cushion layer and the polishing layer were laminated so that the surfaces coated with the heat-sealing adhesive were in contact with each other, and the cushion layer and the polishing layer were laminated with a pressure roller at a temperature of about 140 (± 5) ° C and a pressure of 2 kgf / cm. 2 The resulting mixture was laminated under a pressure of 1000 to 2000 to prepare a polishing pad.
[0262] (Comparative Example B1: Production of Polishing Pad) Step (1) Preparation of urethane-based prepolymer 2,4-toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), dicyclohexylmethane diisocyanate (H12MDI), polytetramethylene ether glycol (PTMEG), and diethylene glycol (DEG) were placed in a four-neck flask and reacted at 80°C for 3 hours to prepare a urethane prepolymer with a terminal NCO group content (NCO%) of 9.1% by weight.
[0263] Step (2) Preparation of the polishing layer A casting machine equipped with tanks and supply lines for supplying raw materials such as prepolymer, curing agent, inert gas, and blowing agent was prepared. The urethane-based prepolymer prepared above, curing agent (4,4'-methylenebis(2-chloroaniline, MOCA), solid-phase blowing agent (Expancel® 551 DE 40 d42, Akzonobel), inert gas (N 2 ), and a silicone surfactant (EVONIK) were filled into each tank. Specifically, 25 parts by weight of a curing agent, 2.2 parts by weight of a solid phase foaming agent, and 1 part by weight of a surfactant were filled relative to 100 parts by weight of the prepolymer, and an inert gas was introduced at a rate of 1.5 L / min.
[0264] The raw materials were stirred while being fed into the mixing head at a constant speed through their respective feeding lines. The rotation speed of the mixing head was about 5000 rpm. The mixed composition of the raw materials was mixed in the mixing head and then poured into a mold having a length of 1000 mm, a width of 1000 mm, and a height of 3 mm. The temperature of the mold was adjusted to about 80 (± 5) °C. The mixed composition was solidified in the mold and cast into a sheet. The sheet was post-cured at about 110 (± 5) °C for about 18 hours to prepare a polishing layer.
[0265] Step (3) Manufacturing the polishing pad One side of the polishing layer was turned using a cutting tool, and grooves were machined using a tip to produce an average thickness of 2 mm. A cushion layer made of polyester fiber nonwoven fabric impregnated with polyurethane resin was provided, and a heat-sealing adhesive was applied to one side of the cushion layer and to the back side of the groove-forming surface of the polishing layer. The cushion layer and the polishing layer were laminated so that the surfaces coated with the heat-sealing adhesive were in contact with each other, and a pressure roller was used to apply pressure at a temperature of about 140 (± 5) ° C and 2 kgf / cm. 2 The resulting mixture was laminated under a pressure of 1000 to 2000 to prepare a polishing pad.
[0266] (Test Example B1: Polishing Pad Physical Property Measurement) The polishing layer, support layer, and polishing pad formed by laminating these layers prepared as described above were subjected to the following tests.
[0267] (1)Hardness The samples were cut into 5 cm x 5 cm (thickness: 2 mm) and stored at room temperature, 30°C, 50°C, and 70°C for 12 hours, respectively, and then the Shore D hardness and Asker C hardness were measured using a hardness tester.
[0268] (2) Specific gravity The sample was cut into a size of 2 cm x 5 cm (thickness: 2 mm) and stored at 25°C for 12 hours, after which the specific gravity was measured using a specific gravity meter.
[0269] (3) Tensile strength The sample was cut into a size of 4 cm×1 cm (thickness: 2 mm), and the maximum strength value just before the breakage of the polishing pad was measured using a universal testing machine (UTM) at a speed of 50 mm / min.
[0270] (4) Growth rate The sample was cut to 4 cm x 1 cm (thickness: 2 mm) and the maximum deformation just before the polishing pad broke was measured using a universal testing machine (UTM) at a speed of 50 mm / min. The ratio of the maximum deformation to the initial length was then expressed as a percentage (%). The results are summarized in the table below. JPEG2025018957000006.jpg103102
[0271] As can be seen from the table, the polishing pad of Example B1 was determined to have physical properties suitable for the CMP process.
[0272] (Test example B2: Change in debris size due to UV irradiation) (1) Conditioning process A porous polyurethane polishing pad was attached and set on the platen of the CMP polishing device. After that, the debris of the polishing layer was collected using only the conditioner and ceria slurry, excluding the operation of the carrier. The platen speed was set at 93 rpm, the conditioner load was 9 lb, the conditioner speed was 64 rpm, and the sweep speed was set at 19 times / min. The polishing layer was conditioned using CI45 (pad cutting rate 80-90 μm / hr, Sesol Co., Ltd.) as a conditioner disk while injecting ceria slurry at 250 mL / min. The debris of the polishing layer generated after 10 minutes of conditioning was collected in a solution state mixed with the ceria slurry to obtain 300 mL of debris solution.
[0273] (2)UV irradiation Using a UV lamp (light source type: mercury lamp), the debris solution obtained above was irradiated with UV light (wavelength 100 to 380 nm) at an intensity of 1 kW from a distance of 5 cm for 10 minutes, while the debris solution was sampled at 2-minute intervals. The debris solution sampled at this time had a pH level of approximately 10.
[0274] (3) Particle size analysis of debris The D50 particle size of the debris in the debris solution was obtained using a particle size analyzer (Mastersize 3000, Malvern) and a medium capacity automated wet disperser (Hydro MV, Malvern). The analyzer settings were: analyte refractive index of polyurethane 1.55, dispersant refractive index of deionized water 1.33, and stirring speed of 2500 rpm. The results are shown in Figures 5 and 6, and Tables 6 and 7 below. JPEG2025018957000007.jpg6385
[0275] JPEG2025018957000008.jpg7185
[0276] As can be seen from Tables 6 and 7 and Figures 5 and 6, the debris particle size of the polishing pad of Example B1 decreased as the UV light irradiation time increased, being measured to be smallest at 2 to 4 minutes, and then showed a tendency to increase slightly as the UV light irradiation time increased to 6 to 8 minutes, but overall showed a tendency for the debris particle size to decrease as the UV light irradiation time increased.
[0277] On the other hand, the polishing pad of Comparative Example B1 generally showed a tendency for the debris particle size to increase as the UV light irradiation time increased, and after 10 minutes, it was measured to have increased to nearly twice the initial size.
[0278] (Test Example B3: Polishing Pad Performance Evaluation (CMP and UV Irradiation)) As shown in FIG. 7 and FIG. 8, a UV lamp 700 capable of adjusting the angle and height was installed in the CMP polishing apparatus. After a silicon wafer having a diameter of 300 mm on which silicon oxide was deposited by a CVD process was installed in the CMP polishing apparatus, the silicon wafer was placed on the platen to which the porous polyurethane polishing pad was attached, with the silicon oxide film of the silicon wafer facing down. Then, under the conditions of a polishing load of 4.0 psi and a polishing pad rotation speed of 150 rpm, calcined ceria slurry was poured onto the polishing pad at a rate of 250 mL / min while the platen was rotated at 150 rpm for 60 seconds to polish the silicon oxide film. During CMP polishing, the UV lamp 700 was operated to irradiate the polishing layer surface of the polishing pad with UV light (wavelength 100 to 380 nm) at an intensity of 1 kW from a distance of 5 cm.
[0279] (1)Removal rate After polishing as described above, the silicon wafer was removed from the carrier, mounted on a spin dryer, washed with deionized water (DIW), and then dried with nitrogen for 15 seconds. The change in film thickness of the dried silicon wafer before and after polishing was measured using a spectroscopic interference wafer thickness meter (model name: SI-F80R, Keyence Corporation).
[0280] Then, the polishing rate was calculated using the following mathematical formula 1. [Number 1] Polishing rate (Å / min) = Change in film thickness before and after polishing (Å) / Polishing time (min)
[0281] (2) Defects Using a CMP polishing device, polishing was performed in the same manner as in the above polishing rate test. After polishing, the silicon wafer was moved to a cleaning machine and washed with 1% HF, 1% H 2 NO 3The wafers were then washed with deionized water (DIW) for 10 seconds each. They were then transferred to a spin dryer, washed with deionized water (DIW), and dried with nitrogen for 15 seconds. The dried silicon wafers were measured for defect changes before and after polishing using a defect measurement device (model name: XP+, KLA-TENCOR). Specifically, the total number of scratches, chatter marks, pits, and residues on the wafers were measured.
[0282] (3) Pad wear rate (PWR) The polishing pad was preconditioned with deionized water for the first 10 minutes, and then conditioned for 1 hour by spraying deionized water. The thickness change was measured during the 1 hour conditioning. The conditioning device was CTS's AP-300HM, the conditioning pressure was 6 lbf, the rotation speed was 100-110 rpm, and the disk used for conditioning was Sesol's CI-45. JPEG2025018957000009.jpg36147
[0283] As a result of the test, the polishing pads of the examples had a polishing rate and a pad wear rate both within the preferred range, and had very few defects, whereas the polishing pads of the comparative examples had a polishing rate outside the preferred range, and the occurrence of defects was also increased. [Explanation of symbols]
[0284] 100: Polishing pad 150: Debris 200: Platen 300: Conditioner 400: Slurry feeder 450: Polishing slurry (CMP slurry) 510: Polishing head 520: Career 600: Semiconductor substrate (wafer) 650: Defect 700:UV lamp 750:UV light
Claims
1. Includes an abrasive layer, The polishing layer includes a urethane-based prepolymer, a foaming agent, and a curing agent, The polishing pad has a D50 particle size of the resulting debris of 50 μm or less under a pH of 5.5 condition when the polishing layer is conditioned for 10 minutes under conditions of a platen speed of 93 rpm, a conditioner load of 9 lb, a conditioner speed of 64 rpm, and a sweep rate of 19 times / min while supplying 300 cc / min of deionized water, and has a zeta potential of −20 mV to 30 mV under a pH of 5.5 condition of an aqueous solution containing the debris at a concentration of 0.01% by weight.
2. The D50 particle size of the debris obtained when conditioning the polishing layer is Under pH 5.5 conditions, it is 25 μm or less, The polishing pad according to claim 1 , which has a particle size of 22.3 μm or less under a pH 10 condition.
3. 2. The polishing pad according to claim 1, wherein the zeta potential of an aqueous solution containing debris obtained during conditioning of the polishing layer at a concentration of 0.01% by weight is −50 mV to −10 mV under a pH 10 condition.
4. 2. The polishing pad according to claim 1, wherein when a silicon oxide film of a silicon wafer is polished with a ceria slurry using the polishing pad, the polishing rate is 2200 Å / min to 2600 Å / min according to the following mathematical formula 1: [Equation 1] Polishing rate (Å / min) = change in film thickness before and after polishing (Å) / polishing time (min).
5. A polishing layer including a polyurethane resin, A polishing pad in which debris obtained when the polishing layer is irradiated with UV light having a wavelength of 100 nm to 380 nm at an intensity of 1 kW from a distance of 5 cm after conditioning the polishing layer under conditions of a platen speed of 93 rpm, a conditioner load of 9 lb, a conditioner speed of 64 rpm, and a sweep rate of 19 times / min while supplying 250 mL / min of ceria slurry: D50 [0 minutes] > D50 [4 minutes]. .. .. (1) Here, D50[0 min] is the D50 particle size of the debris obtained by conditioning before the UV light irradiation, and D50[4 min] is the D50 particle size of the debris obtained when irradiated with UV light for 4 minutes after the conditioning.
6. The polishing pad according to claim 5, wherein ΔD50 [0-4 min] calculated by the following formula is 10 μm or more: △D50 [0-4 minutes] = D50 [0 minutes] - D50 [4 minutes] Where: D50[0 min] is the D50 particle size of the debris obtained by conditioning before the UV light irradiation, D50 [4 min] is the D50 particle size of the debris obtained when irradiated with UV light for 4 minutes after the conditioning.
7. The polishing pad according to claim 5 , wherein the D50 [4 min] is 30 μm or less.
8. 6. The polishing pad of claim 5, wherein the pad wear rate (PWR) when the polishing pad is tested at a conditioning pressure of 6 lbf and a rotation speed of 100 to 110 rpm is 15 μm / hr to 40 μm / hr.
9. 10. A method for manufacturing a semiconductor device, comprising the step of polishing a surface of a semiconductor substrate with the polishing pad according to claim 1.
10. A method for manufacturing a semiconductor device, comprising: chemically and mechanically polishing a semiconductor substrate using the polishing pad according to claim 5; and conditioning a polishing layer of the polishing pad while irradiating the polishing pad with UV light having a wavelength of 100 nm to 380 nm.
Citation Information
Patent Citations
Polyurethane polishing pad
JP2016043479A
Manufacturing method for polishing layer for polishing pad, polishing layer for polishing pad and polishing pad
JP2018176365A
Polishing pad and polishing method using same
WO2018021428A1
KR2016-0027075